Crystal of triphenol compound and method for producing same
By using toluene or cyclohexane as a solvent, the crystallization of characteristic triphenol compounds was obtained, which solved the problem of excessive solvent usage and solid adhesion in the prior art, and achieved an efficient and safe production process.
Patent Information
- Application Number
- CN202380058369.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-16
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
AI Technical Summary
The existing crystallization method of triphenol compounds has problems such as excessive solvent usage and solid adhesion to the inner wall of the device, resulting in low production efficiency and safety risks.
Toluene or cyclohexane as the solvent was used to obtain characteristic crystals (crystalline II,crystalline II-a,crystalline II-b) through differential scanning calorimetry analysis and powder X-ray diffraction analysis, and dried by heating and under reduced pressure to remove the solvent.
The solvent usage is effectively reduced, the solid adhesion problem is avoided, the production efficiency and safety are improved, and the high purity and low solvent content of triphenol compounds are obtained.
Smart Images

Figure CN119630631A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a crystal of a triphenol compound and a method for producing the same. Background Art
[0002] Triphenol compounds can be used for electronic materials, for example, and specifically, can be used as raw materials for photosensitive materials in resist materials or additives for promoting or inhibiting the effect of dissolving in a developer. In this context, polynuclear phenols are required to be high-purity and not contain a large amount of solvent components. If a large amount of solvent components are contained, operations such as solvent replacement are required to remove the contained solvent components, which is disadvantageous from the perspective of industrial production.
[0003] As one type of trisphenol compound, a trisphenol compound represented by chemical formula (A) (4,4′-(1-(4-(2-(4-hydroxy-3-methylphenyl)propan-2-yl)phenyl)ethane-1,1-diyl)bis(2-methylphenol), hereinafter sometimes referred to as compound A) is conventionally known (Patent Documents 1 to 5).
[0004] [Chemistry 1]
[0005] Patent Literature Patent Document 1: Korean Patent Publication No. 10-2017-0006311 Patent Document 2: U.S. Patent No. 4954603 Patent Document 3: Japanese Patent Application Laid-Open No. 62-084035 Patent Document 4: Japanese Patent Application Laid-Open No. 04-251849 Patent Document 5: Japanese Patent Application Laid-Open No. 10-97075 Summary of the invention Patent Documents 1 to 5 describe synthesis examples of Compound A and two crystallization methods. Specifically, (1) a crystallization method using a mixed solvent of toluene and MIBK (Patent Document 1) and (2) a crystallization method using decane as a solvent (Patent Documents 2 to 5) are described, and it is described that the melting point of the crystals of Compound A obtained by these crystallization methods is 87 to 91°C.
[0006] This time, the present inventors conducted experiments on conventionally known crystallization methods (1) and (2) of Compound A based on methods described in patent documents.
[0007] According to the experimental results of the crystallization method (1) described in Patent Document 1, as described in Comparative Example 1 described later, it was clarified that the problem of crystal precipitation was not observed.
[0008] The experimental results of the crystallization method (2) described in Patent Documents 2 to 5, as described in Comparative Example 2 below, revealed that a very large amount of solvent (20 times or more the weight of the solvent relative to the weight of the compound A) is required to completely dissolve the compound A.
[0009] In addition, it is also clear from the results of the crystallization operation that a large amount of the solid of compound A precipitated from the solution will adhere to the inner wall of the crystallization device. When this problem occurs in industrial production, the inability to discharge the solid from the device will significantly reduce the yield, and it will not be possible to maintain continuous production. The cleaning operation for removing the adhered solid may take time, and sometimes it is necessary for the operator to enter the manufacturing device and perform the cleaning operation by hand, which is a highly dangerous operation.
[0010] These studies have revealed that the conventionally known solid of compound A having such properties and the conventionally known crystallization method (2) are not suitable for industrial production or are extremely inefficient due to the above-mentioned problems.
[0011] An object of the present invention is to provide a method for solving the above-mentioned problems associated with Compound A.
[0012] In order to solve the above-mentioned problems, the present inventors conducted intensive studies on the crystallization method of compound A. As a result, as described below, according to the crystallization method using toluene or cyclohexane as a solvent, it is possible to solve the problems of the conventionally known crystallization methods, and the crystals obtained by this method (hereinafter referred to as "Crystals II", "Crystals II-a", "Crystals II-b") can solve the problems existing in the conventionally known solids of compound A, thereby completing the present invention.
[0013] However, it was also found that the crystals obtained by the above method still contained a large amount of solvent after being heated and dried under reduced pressure. In addition, it was also speculated that they were solvated crystals, and the solvent contained in the crystals could not be removed without melting. However, when melting was performed, there was another problem that the powder shape that was easy to handle would be destroyed.
[0014] Therefore, as a result of further studies, the present inventors have found that the above-mentioned problems can be solved together with the above-mentioned other problems according to a specific crystal and a method for producing the same, thereby completing the present invention.
[0015] The present invention is as follows.
[0016] 1. A crystal of a trisphenol compound represented by chemical formula (A), characterized in that the peak top temperature of the endothermic peak obtained by differential scanning calorimetry is in the range of 168 to 180° C. [Chemistry 2] .
[0017] 2. The crystal according to 1., characterized in that the loose bulk density is 0.3-0.8 g / cm 3 range.
[0018] 3. The crystal according to 1., wherein the content of the organic solvent in the crystal is 10 wt % or less.
[0019] 4. The crystal according to 1., wherein the purity represented by area % in liquid chromatography analysis is in the range of 90% to 100%.
[0020] 5. A method for producing the crystal according to 1., characterized in that crystallization is carried out from a solution containing the triphenol compound represented by the chemical formula (A) and an alkylbenzene solvent having a total carbon number of 8 to 10.
[0021] 6. A method for producing the crystal according to 1., characterized in that crystallization is carried out by mixing a chain aliphatic hydrocarbon solvent having 5 to 10 carbon atoms into a solution containing the triphenol compound represented by the chemical formula (A) and a carboxylic acid ester solvent having a total carbon number of 4 to 8.
[0022] 7. A method for producing the crystal according to 1., characterized in that water is mixed into a solution containing the triphenol compound represented by the chemical formula (A) and an alcohol solvent having 1 to 4 carbon atoms to perform crystallization.
[0023] 8. A method for producing the crystals described in 1., characterized in that the crystals of the triphenol compound represented by the chemical formula (A) are heated to 30°C to 170°C, and the peak top temperature of the endothermic peak of the crystals obtained by differential scanning calorimetry analysis has one peak top temperature in the range of 76-86°C and one peak top temperature in the range of 168-180°C.
[0024] 9. A method for producing the crystals described in 1., characterized in that the crystals of the triphenol compound represented by the chemical formula (A) are melted to distill off toluene, and then cooled, wherein the crystals have peaks at diffraction angles 2θ of 14.8°±0.2°, 15.2°±0.2°, 17.5°±0.2° and 18.1°±0.2° in a powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0025] 10. A method for producing the crystals described in 1., characterized in that crystals of the triphenol compound represented by the chemical formula (A) are melted to distill off cyclohexane, and then cooled, wherein the crystals have peaks at diffraction angles 2θ of 11.4°±0.2°, 16.6°±0.2°, and 17.8°±0.2° in a powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0026] 11. A crystal of a triphenol compound represented by chemical formula (A), characterized in that it has peaks at diffraction angles 2θ of 13.9°±0.2°, 15.8°±0.2° and 17.0°±0.2° in a powder X-ray diffraction peak pattern obtained by Cu-Kα radiation, [Chemistry 3] .
[0027] 12. The crystal according to 11., characterized in that the loose bulk density is 0.3-0.5 g / cm 3 range.
[0028] 13. The crystal according to 11., wherein the content of the organic solvent in the crystal is 5% by weight or less.
[0029] 14. The crystal according to 11., wherein the purity represented by area % in liquid chromatography analysis is in the range of 90% to 100%.
[0030] 15. A method for producing the crystal according to 11., characterized in that crystallization is carried out from a solution containing the triphenol compound represented by the chemical formula (A) and an alkylbenzene solvent having a total carbon number of 8 to 10, and the crystals are precipitated at a temperature of the solution in the range of 50 to 75°C.
[0031] 16. A method for producing the crystal according to 11., characterized in that crystallization is carried out by mixing a chain aliphatic hydrocarbon solvent having 5 to 10 carbon atoms into a solution containing the triphenol compound represented by the chemical formula (A) and a carboxylic acid ester solvent having a total carbon number of 4 to 8, and the crystals are precipitated at a temperature of the solution in the range of 50 to 110°C.
[0032] 17. A method for producing the crystals described in 11., characterized in that the crystals of the triphenol compound represented by the chemical formula (A) are heated to a temperature of 30°C to 170°C, wherein the crystals have peaks at diffraction angles 2θ of 13.9°±0.2°, 15.0°±0.2°, 15.8°±0.2° and 17.0°±0.2° in a powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0033] 18. A method for producing the crystals described in 11., characterized in that the crystals of the triphenol compound represented by the chemical formula (A) are melted to distill off toluene, and then cooled, wherein the crystals have peaks at diffraction angles 2θ of 14.8°±0.2°, 15.2°±0.2°, 17.5°±0.2° and 18.1°±0.2° in a powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0034] 19. A method for producing the crystals described in 11., characterized in that crystals of the triphenol compound represented by the chemical formula (A) are melted to distill off cyclohexane, and then cooled, wherein the crystals have peaks at diffraction angles 2θ of 11.4°±0.2°, 16.6°±0.2° and 17.8°±0.2° in a powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0035] 20. A crystal of a triphenol compound represented by chemical formula (A), characterized in that, in a powder X-ray diffraction peak pattern obtained by Cu-Kα radiation, it has peaks at diffraction angles 2θ of 13.9°±0.2°, 15.0°±0.2°, 15.8°±0.2°, and 17.0°±0.2°, [Chemistry 4] .
[0036] 21. A method for producing the crystal according to 20., characterized in that crystallization is carried out by mixing water into a solution containing the triphenol compound represented by the chemical formula (A) and methanol.
[0037] 22. A crystal of a triphenol compound represented by chemical formula (A), characterized in that it has peaks at diffraction angles 2θ of 11.4°±0.2°, 14.0°±0.2° and 16.3°±0.2° in a powder X-ray diffraction peak pattern obtained by Cu-Kα radiation, [Chemistry 5] .
[0038] 23. The crystal according to 22., characterized in that the loose bulk density is 0.4-0.8 g / cm 3 range.
[0039] 24. The crystal according to 22., wherein the content of the organic solvent in the crystal is 5% by weight or less.
[0040] 25. The crystal according to 22., wherein the purity represented by area % in liquid chromatography analysis is in the range of 90% to 100%.
[0041] 26. A method for producing the crystal according to 22., characterized in that crystallization is carried out from a solution containing the triphenol compound represented by the chemical formula (A) and an alkylbenzene solvent having a total carbon number of 8 to 10, and the crystals are precipitated at a temperature of the solution in the range of 10 to 45°C.
[0042] 27. A method for producing the crystal according to 22., characterized in that crystallization is carried out by mixing a chain aliphatic hydrocarbon solvent having 5 to 10 carbon atoms into a solution containing the triphenol compound represented by the chemical formula (A) and a carboxylic acid ester solvent having a total carbon number of 4 to 8, and the crystals are precipitated at a temperature of the solution in the range of 10 to 45°C.
[0043] 28. A crystal of a trisphenol compound represented by chemical formula (A), characterized in that the peak top temperature of the endothermic peak obtained by differential scanning calorimetry is in the range of 103 to 116°C, [Chemistry 6] .
[0044] 29. The crystal according to 28., characterized in that it has peaks at diffraction angles 2θ of 14.8°±0.2°, 15.2°±0.2°, 17.5°±0.2° and 18.1°±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0045] 30. A method for producing the crystal according to 28. or 29., characterized in that crystallization is carried out from a solution containing the triphenol compound represented by the chemical formula (A) and toluene.
[0046] 31. The crystal according to 28., characterized in that it has peaks at diffraction angles 2θ of 11.4°±0.2°, 16.6°±0.2° and 17.8°±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0047] 32. The crystal according to 31., characterized in that the loose bulk density is 0.3-0.6 g / cm 3 range.
[0048] 33. A method for producing the crystal according to 28. or 31., characterized in that crystallization is carried out from a solution containing the triphenol compound represented by the chemical formula (A) and cyclohexane.
[0049] Regarding the crystallization of compound A of the present invention, when compound A is produced by a crystallization operation, in addition to reducing the amount of solvent used, there will be no problem of large amounts of solvent adhering to the inner wall of the crystallization device. Therefore, in the production of compound A, production efficiency and convenience can be improved, and it can be efficiently handled in occasions of industrial utilization such as transportation and use.
[0050] The method for producing crystals of compound A of the present invention can produce the crystals as described above. In addition, the amount of solvent used can be reduced in the production process, and there will be no problem of large amounts of solvent adhering to the inner wall of the device. Therefore, it is a method for efficiently producing crystals of compound A with good convenience. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a graph showing differential scanning calorimetry (DSC) data of Crystal II (Crystal II-a) of Compound A obtained in Example 1.
[0052] Figure 2 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal II-a (Crystal II) of Compound A obtained in Example 1.
[0053] Figure 3 This is a diagram showing a differential scanning calorimetry (DSC) data chart of Crystal I (Crystal α) of Compound A obtained in Example 2.
[0054] Figure 4 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal α (Crystal I) of Compound A obtained in Example 2.
[0055] Figure 5 This is a graph showing differential scanning calorimetry (DSC) data of Crystal I (Crystal α) of Compound A obtained in Example 3.
[0056] Figure 6 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal α (Crystal I) of Compound A obtained in Example 3.
[0057] Figure 7 This is a graph showing differential scanning calorimetry (DSC) data of Crystal I (Crystal β) of Compound A obtained in Example 4.
[0058] Figure 8 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal β (Crystal I) of Compound A obtained in Example 4.
[0059] Fig. 9 This is a diagram showing a differential scanning calorimetry (DSC) data chart of Crystal I (Crystal β) of Compound A obtained in Example 5.
[0060] Fig.10 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal β (Crystal I) of Compound A obtained in Example 5.
[0061] Fig.11 This is a graph showing differential scanning calorimetry (DSC) data of a mixture of Crystal I (Crystal β) and Crystal II (Crystal II-a) of Compound A obtained in Example 6.
[0062] Fig.12 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of a mixture of Crystal β (Crystal I) and Crystal II-a (Crystal II) of Compound A obtained in Example 6.
[0063] Fig.13 This is a diagram showing a differential scanning calorimetry (DSC) data chart of Crystal I (a mixture of Crystal α and Crystal β) of Compound A obtained in Example 7.
[0064] Fig.14 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of a mixture of Crystal α and Crystal β of Compound A obtained in Example 7 (Crystal I).
[0065] Fig.15 This is a diagram showing a differential scanning calorimetry (DSC) data chart of Crystal I (Crystal α) of Compound A obtained in Example 8.
[0066] Fig.16 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal α (Crystal I) of Compound A obtained in Example 8.
[0067] Fig.17 This is a diagram showing a differential scanning calorimetry (DSC) data chart of the crystal Ia (crystal α′) of compound A obtained in Example 9.
[0068] Fig.18 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of the crystal α′ (crystal Ia) of compound A obtained in Example 9.
[0069] Fig.19 This is a diagram showing a differential scanning calorimetry (DSC) data chart of Crystal I (Crystal α) of Compound A obtained in Example 10.
[0070] Fig. 20 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal α (Crystal I) of Compound A obtained in Example 10.
[0071] Fig.21 This is a diagram showing a differential scanning calorimetry (DSC) data chart of the crystal Ia (crystal α′) of compound A obtained in Example 11.
[0072] Fig. 22This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of the crystal α′ (crystal Ia) of compound A obtained in Example 11.
[0073] Fig.23 This is a diagram showing a differential scanning calorimetry (DSC) data chart of [Crystal 12-1] among the crystals of Compound A obtained in Example 12.
[0074] Fig.24 This is a diagram showing a differential scanning calorimetry (DSC) data chart of [Crystal 12-3] among the crystals of Compound A obtained in Example 12.
[0075] Fig.25 This is a diagram showing a differential scanning calorimetry (DSC) data chart of [Crystal 12-4] among the crystals of Compound A obtained in Example 12.
[0076] Fig.26 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of [Crystal 12-2] among the crystals of Compound A obtained in Example 12.
[0077] Fig. 27 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of [Crystal 12-3] among the crystals of Compound A obtained in Example 12.
[0078] Fig.28 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of [Crystal 12-4] among the crystals of Compound A obtained in Example 12.
[0079] Fig.29 This is a diagram showing a differential scanning calorimetry (DSC) data chart of Crystal I (Crystal α) of Compound A obtained in Example 13.
[0080] Fig.30 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal α (Crystal I) of Compound A obtained in Example 13.
[0081] Fig.31 This is a diagram showing a differential scanning calorimetry (DSC) data chart of Crystal I (Crystal β) of Compound A obtained in Example 14.
[0082] Fig.32 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal β (Crystal I) of Compound A obtained in Example 14.
[0083] Fig.33This is a diagram showing a differential scanning calorimetry (DSC) data chart of Crystal I (Crystal β) of Compound A obtained in Example 15.
[0084] Fig.34 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal β (Crystal I) of Compound A obtained in Example 15.
[0085] Fig.35 This is a diagram showing a differential scanning calorimetry (DSC) data chart of Crystal II (Crystal II-b) of Compound A obtained in Example 16.
[0086] Fig.36 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal II-b (Crystal II) of Compound A obtained in Example 16.
[0087] Fig.37 This is a diagram showing a differential scanning calorimetry (DSC) data chart of Crystal I (Crystal α) of Compound A obtained in Example 17.
[0088] Fig.38 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal α (Crystal I) of Compound A obtained in Example 17.
[0089] Fig.39 This is a diagram showing a differential scanning calorimetry (DSC) data chart of Crystal II (Crystal II-b) of Compound A obtained in Example 18.
[0090] Fig.40 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of Crystal II-b (Crystal II) of Compound A obtained in Example 18.
[0091] Fig.41 This is a diagram showing a differential scanning calorimetry (DSC) data chart of the crystals of Compound A obtained in Reference Example 2.
[0092] Fig.42 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of the crystal of Compound A obtained in Reference Example 2.
[0093] Fig.43 This is a diagram showing a differential scanning calorimetry (DSC) data chart of the crystals of Compound A obtained in Reference Example 4.
[0094] Fig.44 This is a diagram showing a powder X-ray diffraction (PXRD) measurement chart of the crystal of Compound A obtained in Reference Example 4. DETAILED DESCRIPTION
[0095] The synthesis method of the trisphenol compound represented by the chemical formula (A) according to the present invention is not particularly limited, and the trisphenol compound can be synthesized by a known method.
[0096] For example, as shown in the following reaction formula, the trisphenol compound represented by the chemical formula (A) can be synthesized by reacting o-cresol and p-isopropenylacetophenone in the presence of an acid catalyst.
[0097] [Chemistry 7]
[0098] In addition, for example, the synthesis can be carried out by the method described in Chinese Patent No. 107011124, Korean Patent No. 10-1786888, and International Publication No. 2010 / 134559.
[0099] The reaction liquid containing the triphenol compound represented by the chemical formula (A) obtained by the above synthesis reaction can be subjected to the neutralization of the catalyst used in the reaction and the removal of unnecessary components such as raw materials or catalysts and reaction solvents exceeding the theoretical amount of the reaction by water washing or distillation according to the usual method. When synthesizing compound A as shown in the above reaction formula, it is preferred that the raw material o-cresol is used in an amount exceeding the theoretical amount of the reaction. In this case, the o-cresol remaining after the reaction is removed by distillation for the crystallization step described later. In addition, the compound A contained in the reaction liquid can be dissolved and mixed with an organic solvent that separates from water to prepare a solution of compound A and then wash with water.
[0100] Then, if necessary, the solvent of the liquid containing compound A can be removed by distillation or the like, or a crystallization solvent can be mixed and separated by crystallization or column chromatography to isolate compound A.
[0101] The crystals of compound A involved in the present invention are produced by using a liquid obtained by treating the reaction solution as described above, a solid obtained by a conventionally known method, the crystal of the present invention or a mixture of polymorphs containing the crystal, or other crystals or solids obtained by the method of the comparative example or reference example described later, and performing the crystallization step described later.
[0102] <Crystallization I> The crystal of the trisphenol compound represented by the chemical formula (A) of the present invention has an endothermic peak top temperature in the range of 168 to 180° C. obtained by differential scanning calorimetry. Hereinafter, this crystal may be referred to as “crystal I”. The peak top temperature is preferably in the range of 170 to 180° C., and more preferably in the range of 175 to 180° C.
[0103] The crystal of the trisphenol compound represented by the chemical formula (A) of the present invention may show one endothermic peak in the range of 168 to 180° C. by differential scanning calorimetry, or may show two endothermic peaks, one and another, in the range of 168 to 180° C. Among them, the case where one endothermic peak appears is preferred.
[0104] When two endothermic peaks appear by differential scanning calorimetry, one may appear in the range of 168 to 180°C and the other may appear in the range of 76 to 86°C. Hereinafter, the crystal having this characteristic may be referred to as "crystal Ia". The crystal in this case is presumed to be a crystal obtained by solvation with an alcohol solvent having 1 to 4 carbon atoms, and the endothermic peak in the range of 76 to 86°C is presumed to represent the endothermic absorption when the alcohol solvent having 1 to 4 carbon atoms in the crystal is desolvated, and the endothermic peak in the range of 168 to 180°C is presumed to represent the endothermic absorption when the crystal melts after desolvation. As the alcohol solvent having 1 to 4 carbon atoms, methanol is particularly preferred.
[0105] Although the crystals of compound A of the present invention in this form are obtained by solvation with an alcohol solvent having 1 to 4 carbon atoms, the solvent can be removed without melting, and thus it is preferred to obtain crystals I (or "crystals α" described later) which have a low solvent content and are easy to handle in a powdery state.
[0106] In other cases where two endothermic peaks appear by differential scanning calorimetry, one may appear in the range of 103 to 112°C and the other may appear in the range of 168 to 180°C. As such, for example, when toluene is contained in the solution when crystallizing compound A, "crystal II" described later may also precipitate simultaneously. The mixture with the crystal of the present invention can be determined to be a mixture of two or more crystals by analyzing the crystal phase by powder X-ray diffraction analysis, for example.
[0107] The loose bulk density of the crystal I of the compound A is preferably 0.3 to 0.8 g / cm 3 The loose bulk density is more preferably 0.33 to 0.75 g / cm 3 The range is more preferably 0.45 to 0.7 g / cm 3 The range is particularly preferably 0.5 to 0.7 g / cm 3 range.
[0108] Crystal I in this form is preferred because it has a high bulk density which is sufficiently advantageous in industrial production and is therefore easy to handle and contributes to efficient production of compound A.
[0109] The content of the organic solvent in the crystal I of compound A is preferably 10 wt % or less. The content of the organic solvent is more preferably 6 wt % or less, further preferably 4 wt % or less, and particularly preferably 2 wt % or less.
[0110] This form of crystal I is suitable for the storage and transportation of compound A because it contains less solvent. In addition, the equivalent number can be easily optimized when manufacturing a resin or derivative using the crystal I, thereby reducing the exposure to the solvent volatilized during manufacturing, which helps protect the health of handling workers and the environment, and is therefore preferred.
[0111] The purity of the crystal I of compound A expressed as area % in the analysis based on liquid chromatography is preferably in the range of 90% to 100%. The purity is more preferably in the range of 93% to 100%, further preferably in the range of 95% to 100%, and particularly preferably in the range of 98% to 100%.
[0112] The method for producing the crystal I of compound A of the present invention includes the following production methods 1 to 6. Among them, production method 1, 2, 3 or 4 is preferred from the viewpoint of producing a crystal of compound A that can be easily handled in a powder form.
[0113] Production method 1, 2 or 4 is more preferred from the viewpoint that the solvent contained in the crystals can be removed without melting, the solvent content is small, and crystals of compound A which can be easily handled in a powder form are produced.
[0114] Production method 1 or 2 is particularly preferred from the viewpoint of producing a powdery crystal of Compound A which is not solvated with the solvent in the crystallization liquid during crystal precipitation and can remove the solvent by drying without melting and desolvation.
[0115] <Method 1 for producing crystal I> One of the methods for producing the crystal I of compound A of the present invention is a method of crystallizing from a solution containing compound A and an alkylbenzene solvent having a total carbon number of 8 to 10.
[0116] Specific examples of the alkylbenzene solvent having a total carbon number of 8 to 10 include ethylbenzene, p-xylene, m-xylene, o-xylene (total carbon number 8), mesitylene, 2-ethyltoluene, 3-ethyltoluene, 4-ethyltoluene (total carbon number 9), tetralin, 1,2-diethylbenzene, 1,3-diethylbenzene, and 1,4-diethylbenzene (total carbon number 10). Among them, the alkylbenzene solvent having a total carbon number of 8 is preferred, and ethylbenzene is particularly preferred.
[0117] Among these alkylbenzene solvents, one or more kinds may be used, and the content ratio is not particularly limited. A mixture of ethylbenzene, p-xylene, m-xylene and o-xylene, so-called mixed xylene, may also be used.
[0118] The combination of types of alkylbenzenes having a total carbon number of 8 to 10 is preferably a combination selected from ethylbenzene, p-xylene, m-xylene and o-xylene, and the mixing ratio thereof is preferably 70 to 90 wt % of p-xylene, m-xylene and o-xylene in total and 10 to 30 wt % of ethylbenzene.
[0119] The amount of the solvent used in this case is in the range of 1 to 10 times by weight, more preferably 1.5 to 5 times by weight, further preferably 2 to 4 times by weight, particularly preferably 2 to 3 times by weight, based on the crude crystals or distillation residue of Compound A.
[0120] When the crystal is precipitated, a seed crystal may not be used, but it is preferred to use a seed crystal. The crystal used as the seed crystal is Crystal I, and the crystal precipitated without the seed crystal can be used as the seed crystal.
[0121] The crystals are precipitated when the temperature of the solution is in the range of 10 to 75° C. After the crystals begin to precipitate, the temperature is maintained at the same level to increase the amount of crystals precipitated. The holding time is not particularly limited, but is generally in the range of 1 to 120 hours.
[0122] After the amount of crystals precipitated increases, the liquid containing the crystals may be cooled, and the final cooling temperature is preferably 10 to 30° C. Through the above crystallization operation, crystals I may be precipitated. The precipitated crystals I may be filtered out and isolated by filtration.
[0123] The filtered crystals are preferably dried to remove the solvent used in the crystallization. The drying temperature is in the range of 25 to 140° C., more preferably in the range of 50 to 120° C. The drying may be carried out under normal pressure or under reduced pressure, but when it is industrially implemented, it is preferred to carry out under reduced pressure because the solvent can be removed more efficiently.
[0124] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0125] <Method 2 for producing crystal I> Another method for producing the crystal I of compound A of the present invention is to mix a linear aliphatic hydrocarbon solvent having 5 to 10 carbon atoms into a solution containing compound A and a carboxylic acid ester solvent having 4 to 8 total carbon atoms to perform crystallization.
[0126] Specific examples of the carboxylic acid ester solvent having a total carbon number of 4 to 8 include ethyl acetate (total carbon number 4); ethyl propionate (total carbon number 5); butyl acetate (total carbon number 6); amyl acetate, isoamyl acetate, 2-methylbutyl acetate (total carbon number 7); n-hexyl acetate (total carbon number 8), etc. Among them, butyl acetate is particularly preferred.
[0127] The amount of the carboxylic acid ester solvent having 4 to 8 total carbon atoms used is in the range of 0.3 to 5 times by weight, more preferably 0.5 to 3 times by weight, and particularly preferably 0.5 to 2 times by weight, based on the compound A used.
[0128] As the chain aliphatic hydrocarbon solvent having 5 to 10 carbon atoms, specifically, for example, pentane, hexane, heptane, octane, and isooctane can be used, preferably a chain aliphatic hydrocarbon solvent having 6 to 8 carbon atoms, more preferably hexane, heptane, octane, or isooctane, further preferably hexane or isooctane, and particularly preferably isooctane.
[0129] The amount of the chain aliphatic hydrocarbon solvent having 5 to 10 carbon atoms used is in the range of 0.5 to 10 times by weight, more preferably 1 to 5 times by weight, further preferably 1.5 to 4 times by weight, particularly preferably 1.5 to 3 times by weight, based on the compound A used.
[0130] As the temperature for crystallization, preferably 10 to 110°C. When crystallization is precipitated, seed crystals may not be used, but seed crystals are preferably used. The crystals used as seed crystals are not limited, but preferably crystal I, and the crystals precipitated in the seedless state can be used as seed crystals. As the final cooling temperature, preferably 10 to 30°C. The precipitated crystals can be isolated by filtering out by filtering operation.
[0131] The filtered crystals are preferably dried to remove the solvent used in the crystallization. The drying temperature is in the range of 25 to 140° C., more preferably in the range of 50 to 120° C. The drying may be carried out under normal pressure or under reduced pressure, but when it is industrially implemented, it is preferred to carry out under reduced pressure because the solvent can be removed more efficiently.
[0132] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0133] <Method 3 for producing crystal I> As another method for producing the crystal I of the compound A of the present invention, there is a method of mixing water into a solution containing the compound A and an alcohol solvent having 1 to 4 carbon atoms to perform crystallization. According to this method, in the crystal I, a crystal I having a morphology in which one endothermic peak appears in the range of 76 to 86° C. and another appears in the range of 168 to 180° C. as determined by differential scanning calorimetry can be produced.
[0134] Specific examples of the alcohol solvent having 1 to 4 carbon atoms to be used include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, and 2-butanol. Among them, methanol is particularly preferred.
[0135] The amount of the alcohol solvent having 1 to 4 carbon atoms used is in the range of 0.5 to 5.0 times by weight, preferably 0.5 to 4.5 times by weight, more preferably 0.6 to 2.5 times by weight, and particularly preferably 0.6 to 1.5 times by weight, based on the amount of Compound A used.
[0136] The amount of water to be mixed is in the range of 0.5 to 9.5 times by weight, preferably 0.5 to 4.5 times by weight, more preferably 0.5 to 3.4 times by weight, and particularly preferably 0.5 to 2.4 times by weight, based on the amount of compound A used.
[0137] The amount of the solvent used is in the range of 1 to 10 times by weight, more preferably 1.5 to 5 times by weight, further preferably 2 to 4 times by weight, particularly preferably 2 to 3 times by weight, based on the amount of Compound A used.
[0138] When crystallization is precipitated, seed crystals may not be used, but seed crystals are preferably used. The crystals used as seed crystals are crystals I, and the crystals precipitated without seed crystals can be used as seed crystals. As the final cooling temperature, 10 to 30° C. is preferred. The precipitated crystals can be filtered out by filtering operation.
[0139] The filtered crystals are dried at a temperature in the range of 40 to 70° C., more preferably in the range of 50 to 70° C., to obtain a crystal I having one endothermic peak in the range of 76 to 86° C. and one endothermic peak in the range of 168 to 180° C. by differential scanning calorimetry. The pressure during drying may be either normal pressure or reduced pressure, but in industrial practice, it is preferred to dry under reduced pressure because the solvent can be removed more efficiently.
[0140] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0141] <Method 4 for producing crystal I> The crystal I obtained above, which shows one endothermic peak in the range of 76 to 86° C. and one endothermic peak in the range of 168 to 180° C. by differential scanning calorimetry, can be removed from the crystals without melting the solvent used for crystallization, that is, the alcohol solvent having 1 to 4 carbon atoms, by heating to a temperature in the range of 30 to 170° C., thereby producing the crystal I having an endothermic peak in the range of 168 to 180° C. by differential scanning calorimetry. The heating temperature is preferably in the range of 85 to 150° C., more preferably in the range of 85 to 120° C., and particularly preferably in the range of 85 to 100° C.
[0142] The heating may be carried out under normal pressure or under reduced pressure. However, when carried out industrially, it is preferably carried out under reduced pressure because the solvent can be removed more efficiently.
[0143] Among the alcohol solvents having 1 to 4 carbon atoms contained in the crystals as a solvate, methanol is particularly preferred.
[0144] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0145] <Method 5 for producing crystal I> As another method for manufacturing the crystal I of compound A of the present invention, there is a method of melting the crystal of compound A to distill off toluene, and cooling, wherein the crystal of compound A has peaks at diffraction angles 2θ of 14.8°±0.2°, 15.2°±0.2°, 17.5°±0.2° and 18.1°±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0146] Here, the crystal of Compound A having peaks at diffraction angles 2θ of 14.8°±0.2°, 15.2°±0.2°, 17.5°±0.2° and 18.1°±0.2° in the powder X-ray diffraction peak pattern obtained by Cu—Kα rays is referred to as “Crystal II-a” described below.
[0147] The temperature when melting Crystal II-a and distilling off toluene is in the range of 100 to 150° C. The pressure at this time may be normal pressure or reduced pressure, and it is preferred to distill off toluene under reduced pressure because toluene can be removed more efficiently.
[0148] The molten compound A after the removal of toluene can be solidified by spraying (injecting) in cold air or dropping on a cooling belt to be melt-granulated, thereby producing crystals I of compound A in an easy-to-use shape. The cooling rate at this time is not particularly limited.
[0149] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0150] <Method 6 for producing crystal I> As another method for manufacturing the crystal I of compound A of the present invention, there is a method of melting the crystal of compound A to distill off cyclohexane, and cooling, wherein the crystal of compound A has peaks at diffraction angles 2θ of 11.4°±0.2°, 16.6°±0.2° and 17.8°±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0151] Here, the crystal of Compound A having peaks at diffraction angles 2θ of 11.4°±0.2°, 16.6°±0.2°, and 17.8°±0.2° in the powder X-ray diffraction peak pattern obtained by Cu—Kα rays is referred to as “Crystal II-b” described below.
[0152] The temperature when melting Crystal II-b and distilling off cyclohexane is in the range of 100 to 150° C. The pressure at this time may be normal pressure or reduced pressure, and reduced pressure is preferred because cyclohexane can be distilled off more efficiently.
[0153] The molten compound A after the removal of cyclohexane can be solidified by spraying (injecting) in cold air or dropping on a cooling belt to be melt-granulated, thereby producing crystals I of compound A in an easy-to-use shape. The cooling rate at this time is not particularly limited.
[0154] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0155] <Crystal α> The crystal of the triphenol compound represented by the chemical formula (A) of the present invention has peaks at diffraction angles 2θ of 13.9°±0.2°, 15.8°±0.2°, and 17.0°±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays. The crystal preferably further has a peak at a diffraction angle 2θ of 20.8°±0.2°, and more preferably has a peak at a diffraction angle 2θ of 16.6°±0.2° and 25.6°±0.2°. Hereinafter, the crystal is sometimes referred to as "crystal α". Compared with the "crystal α'" described later, the absence of a peak at a diffraction angle 2θ of 15.0°±0.2°, and the absence of a peak at a diffraction angle 2θ of 7.5°±0.2° and 22.5°±0.2°, is sometimes an element for distinguishing "crystal α" from "crystal α'". In addition, based on the peak with the largest intensity, the relative intensity of these peaks is preferably greater than 10, and more preferably greater than 25. However, the relative intensity sometimes varies depending on the measuring device or conditions, and in the case of a mixture with other crystals. Therefore, the crystalline phase can be identified based on the analytical method of conventional powder X-ray diffraction analysis.
[0156] The loose bulk density of the crystal α of compound A is preferably 0.3 to 0.5 g / cm 3 The loose bulk density is more preferably 0.3 to 0.45 g / cm 3 The range is more preferably 0.33 to 0.45 g / cm 3 The range is particularly preferably 0.33 to 0.4 g / cm 3 range.
[0157] Crystal α in this form has a high bulk density that is sufficiently advantageous in terms of industrial production, and is therefore easy to handle, and contributes to efficient production of compound A, and is therefore preferred.
[0158] The content of the organic solvent in the crystal α of compound A is preferably 5 wt % or less, more preferably 4 wt % or less, further preferably 3 wt % or less, and particularly preferably 2 wt % or less.
[0159] This form of crystalline α is suitable for the storage and transportation of compound A due to its low solvent content. In addition, the equivalent number when manufacturing a resin or derivative using the crystalline α can be easily optimized, thereby reducing the exposure to the solvent volatilized during manufacturing, which helps to protect the health of handling workers and the environment, and is therefore preferred.
[0160] The purity of the crystal α of compound A expressed by area % in liquid chromatography analysis is preferably in the range of 90% to 100%, more preferably in the range of 93% to 100%, further preferably in the range of 95% to 100%, and particularly preferably in the range of 98% to 100%.
[0161] The peak top temperature of the endothermic peak of the crystal α of compound A obtained by differential scanning calorimetry analysis may be in the range of 168 to 180° C. The peak temperature is preferably in the range of 170 to 180° C., and more preferably in the range of 175 to 180° C.
[0162] The method for producing the crystal α of compound A of the present invention includes the following production methods 1 to 5. Among them, production method 1, 2 or 3 is preferred from the viewpoint that the solvent contained in the crystal can be removed without melting, the solvent content is small, and the crystal of compound A can be easily handled in a powder form.
[0163] Among them, Production Method 1 or 2 is more preferred from the viewpoint of producing a powdery crystal of Compound A which is not solvated with the solvent in the crystallization liquid during crystal precipitation and can remove the solvent by drying without melting and desolvation.
[0164] <Method 1 for producing crystal α> One method for producing the crystal α of compound A of the present invention is to crystallize a solution containing compound A and an alkylbenzene solvent having a total carbon number of 8 to 10, and precipitate the crystals at a temperature of 50 to 75°C.
[0165] Specific examples of the alkylbenzene solvent having a total carbon number of 8 to 10 include ethylbenzene, p-xylene, m-xylene, o-xylene (total carbon number 8), mesitylene, 2-ethyltoluene, 3-ethyltoluene, 4-ethyltoluene (total carbon number 9), tetralin, 1,2-diethylbenzene, 1,3-diethylbenzene, and 1,4-diethylbenzene (total carbon number 10). Among them, the alkylbenzene solvent having a total carbon number of 8 is preferred, and ethylbenzene is particularly preferred.
[0166] Among these alkylbenzene solvents, one or more kinds may be used, and the content ratio in this case is not particularly limited. A mixture of ethylbenzene, p-xylene, m-xylene, and o-xylene, i.e., mixed xylene, may also be used.
[0167] The combination of types of alkylbenzenes having a total carbon number of 8 to 10 is preferably a combination selected from ethylbenzene, p-xylene, m-xylene and o-xylene, and the mixing ratio thereof is preferably 70 to 90 wt % of p-xylene, m-xylene and o-xylene in total and 10 to 30 wt % of ethylbenzene.
[0168] The amount of the solvent used in this case is in the range of 1 to 10 times by weight, more preferably 1.5 to 5 times by weight, further preferably 2 to 4 times by weight, particularly preferably 2 to 3 times by weight, based on the crude crystals or distillation residue of Compound A.
[0169] When the crystal is precipitated, a seed crystal may not be used, but it is preferred to use a seed crystal. The crystal used as the seed crystal is crystal α, and a crystal precipitated without a seed crystal can be used as a seed crystal.
[0170] The crystal is precipitated when the temperature of the solution is in the range of 50 to 75° C., preferably in the range of 50 to 70° C., and particularly preferably in the range of 55 to 70° C. After the crystal begins to precipitate, it is maintained at the same temperature to increase the amount of crystal precipitation. There is no particular limitation on the time of maintenance, but it is usually in the range of 1 to 120 hours.
[0171] After the amount of precipitated crystals is increased, the liquid containing the crystals may be cooled, and the final cooling temperature is preferably 10 to 30° C. The precipitated crystals may be isolated by filtering out the precipitated crystals.
[0172] The filtered crystals are preferably dried to remove the solvent used in the crystallization. The drying temperature is in the range of 25 to 140° C., more preferably in the range of 50 to 120° C. The drying may be carried out under normal pressure or under reduced pressure, but when it is industrially implemented, it is preferred to carry out under reduced pressure because the solvent can be removed more efficiently.
[0173] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0174] <Method 2 for producing crystal α> As another method for producing the crystal α of the compound A of the present invention, there is a method in which a solution containing the compound A and a carboxylic acid ester solvent having a total carbon number of 4 to 8 is mixed with a chain aliphatic hydrocarbon solvent having 5 to 10 carbon atoms to perform crystallization, and the crystals are precipitated at a temperature of the solution in the range of 50 to 110°C.
[0175] Specific examples of the carboxylic acid ester solvent having a total carbon number of 4 to 8 include ethyl acetate (total carbon number 4); ethyl propionate (total carbon number 5); butyl acetate (total carbon number 6); amyl acetate, isoamyl acetate, 2-methylbutyl acetate (total carbon number 7); n-hexyl acetate (total carbon number 8), etc. Among them, butyl acetate is particularly preferred.
[0176] The amount of the carboxylic acid ester solvent having 4 to 8 total carbon atoms used is in the range of 0.3 to 5 times by weight, more preferably 0.5 to 3 times by weight, and particularly preferably 0.5 to 2 times by weight, based on the compound A used.
[0177] As the chain aliphatic hydrocarbon solvent having 5 to 10 carbon atoms, specifically, for example, pentane, hexane, heptane, octane, and isooctane can be used, preferably a chain aliphatic hydrocarbon solvent having 6 to 8 carbon atoms, more preferably hexane, heptane, octane, or isooctane, further preferably hexane or isooctane, and particularly preferably isooctane.
[0178] The amount of the chain aliphatic hydrocarbon solvent having 5 to 10 carbon atoms used is in the range of 0.5 to 10 times by weight, more preferably 1 to 5 times by weight, further preferably 1.5 to 4 times by weight, particularly preferably 1.5 to 3 times by weight, relative to the amount of Compound A used.
[0179] When crystallization is precipitated, seed crystals may not be used, but it is preferred to use seed crystals. The crystal used as seed crystals is not limited, but crystal α is preferred, and crystals precipitated without seed crystals may be used as seed crystals.
[0180] The crystal is precipitated when the temperature of the solution is in the range of 50 to 110° C., preferably in the range of 50 to 90° C., more preferably in the range of 50 to 75° C., and particularly preferably in the range of 55 to 70° C. After the crystal begins to precipitate, it is maintained at the same temperature to increase the amount of crystal precipitation. There is no particular limitation on the time of maintenance, which is usually in the range of 1 to 120 hours.
[0181] After the amount of precipitated crystals is increased, the liquid containing the crystals may be cooled, and the final cooling temperature is preferably 10 to 30° C. The precipitated crystals may be isolated by filtering out the precipitated crystals.
[0182] The filtered crystals are preferably dried to remove the solvent used in the crystallization. The drying temperature is in the range of 25 to 140° C., more preferably in the range of 50 to 120° C. The drying may be carried out under normal pressure or under reduced pressure, but when it is industrially implemented, it is preferred to carry out under reduced pressure because the solvent can be removed more efficiently.
[0183] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0184] <Method 3 for producing crystal α> As another method for producing the crystal α of the compound A of the present invention, there is a method of heating a crystal of the compound A having peaks at diffraction angles 2θ of 13.9°±0.2°, 15.0°±0.2°, 15.8°±0.2°, and 17.0°±0.2° in a powder X-ray diffraction peak spectrum obtained by Cu-Kα radiation to a temperature in the range of 30 to 170° C. The crystal of the compound A subjected to this heating is the “crystal α′” described below.
[0185] The heating temperature is preferably in the range of 60 to 150° C., more preferably in the range of 80 to 120° C., and particularly preferably in the range of 80 to 100° C. By heating, the solvated methanol contained in the crystals can be removed without melting the crystals, thereby producing Crystal α.
[0186] The heating may be carried out under normal pressure or under reduced pressure. However, when carried out industrially, it is preferably carried out under reduced pressure because the solvent can be removed more efficiently.
[0187] <Crystal α'> The crystal of compound A of the present invention has a peak at a diffraction angle 2θ of 13.9°±0.2°, 15.0°±0.2°, 15.8°±0.2° and 17.0°±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays. The crystal further preferably has a peak at a diffraction angle 2θ of 20.8°±0.2°, and further preferably has a peak at a diffraction angle 2θ of 25.6°±0.2° and 22.5°±0.2°, and further preferably has a peak at a diffraction angle 2θ of 7.5°±0.2°. Hereinafter, the crystal is sometimes referred to as "crystal α'". In addition, based on the peak with the largest intensity, the relative intensity of these peaks is preferably 10 or more, more preferably 25 or more, but depending on the measuring device or conditions, in addition, in the case of a mixture with other crystals, the relative intensity sometimes changes, so the crystal phase can be identified based on the analysis method of the usual powder X-ray diffraction analysis.
[0188] The analysis of the solvent contained in the crystal and the differential scanning calorimetry analysis indicate that the crystal α' is a crystal that is solvated with methanol. The endothermic peaks obtained by the differential scanning calorimetry analysis show one in the range of 168 to 180°C and another in the range of 76 to 86°C. The endothermic peak in the range of 76 to 86°C indicates that methanol is being desolvated, and the endothermic peak in the range of 168 to 180°C indicates that the crystal is melting after desolvation.
[0189] Crystal α' of Compound A of the present invention can be desolvated from methanol without melting, and can produce Crystal I (Crystal α) having a low solvent content and being easily handled in a powdery state.
[0190] <Method for producing crystal α'> The crystal α' of the compound A of the present invention can be produced by mixing water with a solution containing the compound A and methanol to carry out crystallization.
[0191] The amount of methanol used is 0.5 to 5.0 times by weight, preferably 0.5 to 4.5 times by weight, more preferably 0.5 to 3.0 times by weight, further preferably 0.6 to 1.5 times by weight, particularly preferably 0.6 to 1.0 times by weight, relative to the amount of Compound A used.
[0192] The amount of water to be mixed is in the range of 0.5 to 9.5 times by weight, preferably 0.5 to 4.5 times by weight, more preferably 0.5 to 3.4 times by weight, further preferably 0.5 to 2.5 times by weight, particularly preferably 0.5 to 1.5 times by weight, relative to the amount of compound A used.
[0193] The total amount of the solvents used is 1 to 10 times by weight, more preferably 1.5 to 5 times by weight, further preferably 2 to 4 times by weight, and particularly preferably 2 to 3 times by weight, based on the amount of Compound A used.
[0194] When crystallization is precipitated, seed crystals may not be used, but seed crystals are preferably used. The crystals used as seed crystals are crystals α', and crystals precipitated without seed crystals can be used as seed crystals. As the final cooling temperature, 10 to 30° C. are preferably used. The precipitated crystals can be filtered out by filtering.
[0195] The filtered crystals are dried at a temperature in the range of 40 to 70° C., more preferably in the range of 50 to 70° C., to obtain crystals α' with reduced solvent content. The drying pressure may be either normal pressure or reduced pressure, but in industrial practice, it is preferred to dry under reduced pressure because the solvent can be removed more efficiently.
[0196] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0197] <Method 4 for producing crystal α> As another method for manufacturing the crystal α of compound A of the present invention, there is a method of melting the crystal of compound A to distill off toluene, and cooling, wherein the crystal of compound A has peaks at diffraction angles 2θ of 14.8°±0.2°, 15.2°±0.2°, 17.5°±0.2° and 18.1°±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0198] Here, the crystal of Compound A having peaks at diffraction angles 2θ of 14.8°±0.2°, 15.2°±0.2°, 17.5°±0.2° and 18.1°±0.2° in the powder X-ray diffraction peak pattern obtained by Cu—Kα rays is referred to as “Crystal II-a” described later.
[0199] The temperature when melting Crystal II-a and distilling off toluene is in the range of 100 to 150° C. The pressure at this time is normal pressure or reduced pressure, and it is preferred to distill off toluene under reduced pressure because toluene can be removed more efficiently.
[0200] The molten compound A after the removal of toluene can be solidified by spraying (injecting) in cold air or dropping on a cooling belt to be melt-granulated, thereby producing crystals I of compound A in an easy-to-use shape. The cooling rate at this time is not particularly limited.
[0201] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0202] <Method 5 for producing crystal α> As another method for manufacturing the crystal α of compound A of the present invention, there is a method of melting the crystal of compound A to distill off cyclohexane, and cooling, wherein the crystal of compound A has peaks at diffraction angles 2θ of 11.4°±0.2°, 16.6°±0.2° and 17.8°±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays.
[0203] Here, the crystal of Compound A having peaks at diffraction angles 2θ of 11.4°±0.2°, 16.6°±0.2°, and 17.8°±0.2° in the powder X-ray diffraction peak pattern obtained by Cu—Kα rays is referred to as “Crystal II-b” described below.
[0204] The temperature when melting Crystal II-b and distilling off cyclohexane is in the range of 100 to 150° C. The pressure at this time is normal pressure or reduced pressure, and it is preferred to distill off cyclohexane under reduced pressure because the cyclohexane can be removed more efficiently.
[0205] The molten compound A after the removal of cyclohexane can be solidified by spraying (injecting) in cold air or dropping on a cooling belt to be melt-granulated, thereby producing crystals I of compound A in an easy-to-use shape. The cooling rate at this time is not particularly limited.
[0206] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0207] <Crystal β> The crystal of the triphenol compound represented by the chemical formula (A) of the present invention has peaks at diffraction angles 2θ of 11.4°±0.2°, 14.0°±0.2°, and 16.3°±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays. The crystal further preferably has peaks at diffraction angles 2θ of 18.8°±0.2°, 19.8°±0.2°, and 20.3°±0.2°. Hereinafter, the crystal is sometimes referred to as "crystal β". In addition, based on the peak with the largest intensity, the relative intensity of these peaks is preferably 10 or more, more preferably 25 or more, but depending on the measuring device or conditions, and in the case of a mixture with other crystals, the relative intensity sometimes varies, so the crystal phase can be identified based on the analysis method of the usual powder X-ray diffraction analysis.
[0208] Crystal β of compound A does not solvate with the solvent in the crystallization liquid from the beginning of precipitation, and compound A can be produced in the form of crystals with a low solvent content by drying, and the heat required for desolvation required in other crystals (crystals I-a, crystals II-a, crystals II-b) can be reduced, thereby efficiently producing compound A.
[0209] The loose bulk density of the crystalline β of compound A is preferably 0.4 to 0.8 g / cm 3 The loose bulk density is more preferably 0.45 to 0.75 g / cm 3 The range is more preferably 0.45 to 0.7 g / cm 3 The range is particularly preferably 0.5 to 0.7 g / cm 3 range.
[0210] Crystal β in this form has a high bulk density which is sufficiently advantageous in industrial production, and is therefore easy to handle and contributes to efficient production of compound A, and is therefore preferred.
[0211] The content of the organic solvent in the crystal β of compound A is preferably 5 wt % or less, more preferably 4 wt % or less, further preferably 3 wt % or less, particularly preferably 2 wt % or less.
[0212] This form of crystalline β is suitable for the storage and transportation of compound A due to its low solvent content. In addition, the equivalent number when manufacturing a resin or derivative using the crystalline β can be easily optimized, thereby reducing the exposure to the solvent volatilized during manufacturing, which helps to protect the health of handling workers and the environment, and is therefore preferred.
[0213] The purity of the crystal β of compound A expressed as area % in the analysis based on liquid chromatography is preferably in the range of 90% to 100%. The purity is more preferably in the range of 93% to 100%, further preferably in the range of 95% to 100%, and particularly preferably in the range of 98% to 100%.
[0214] The peak top temperature of the endothermic peak of the crystal β of compound A obtained by differential scanning calorimetry analysis may be in the range of 168 to 180° C. The peak temperature is preferably in the range of 170 to 180° C., and more preferably in the range of 175 to 180° C.
[0215] <Method 1 for producing crystal β> One method for producing the crystalline β of compound A of the present invention is to crystallize compound A from a solution containing compound A and an alkylbenzene solvent having a total carbon number of 8 to 10, and to precipitate crystals at a temperature of 10 to 45°C.
[0216] Specific examples of the alkylbenzene solvent having a total carbon number of 8 to 10 include ethylbenzene, p-xylene, m-xylene, o-xylene (total carbon number 8), mesitylene, 2-ethyltoluene, 3-ethyltoluene, 4-ethyltoluene (total carbon number 9), tetralin, 1,2-diethylbenzene, 1,3-diethylbenzene, and 1,4-diethylbenzene (total carbon number 10). Among them, the alkylbenzene solvent having a total carbon number of 8 is preferred, and ethylbenzene is particularly preferred.
[0217] Among these alkylbenzene solvents, one or more kinds may be used, and the content ratio in this case is not particularly limited. A mixture of ethylbenzene, p-xylene, m-xylene, and o-xylene, i.e., mixed xylene, may also be used.
[0218] The combination of types of alkylbenzenes having a total carbon number of 8 to 10 is preferably a combination selected from ethylbenzene, p-xylene, m-xylene and o-xylene, and the mixing ratio thereof is preferably 70 to 90 wt % of p-xylene, m-xylene and o-xylene in total and 10 to 30 wt % of ethylbenzene.
[0219] The amount of the solvent used in this case is in the range of 1 to 10 times by weight, more preferably 1.5 to 5 times by weight, further preferably 2 to 4 times by weight, particularly preferably 2 to 3 times by weight, based on the crude crystals or distillation residue of Compound A.
[0220] When the crystal is precipitated, a seed crystal may not be used, but it is preferred to use a seed crystal. The crystal used as the seed crystal is crystal β, and the crystal precipitated without the seed crystal can be used as the seed crystal.
[0221] As mentioned above, crystallization is precipitated when the temperature of the solution is in the range of 10 to 45° C., preferably in the range of 15 to 40° C., more preferably in the range of 20 to 40° C., and particularly preferably in the range of 20 to 35° C. After crystallization begins to precipitate, it is maintained at the same temperature to increase the amount of crystallization. There is no particular limitation on the time of maintenance, but it is usually in the range of 1 to 120 hours.
[0222] After the amount of precipitated crystals is increased, the liquid containing the crystals may be cooled, and the final cooling temperature is preferably 10 to 30° C. The precipitated crystals may be isolated by filtering out the precipitated crystals.
[0223] The filtered crystals are preferably dried to remove the solvent used in the crystallization. The drying temperature is in the range of 25 to 140° C., more preferably in the range of 50 to 120° C. The drying may be carried out under normal pressure or under reduced pressure, but when it is industrially implemented, it is preferred to carry out under reduced pressure because the solvent can be removed more efficiently.
[0224] <Method 2 for producing crystal β> As another method for producing the crystalline β of the compound A of the present invention, there is a method in which a linear aliphatic hydrocarbon solvent having 5 to 10 carbon atoms is mixed with a solution containing the compound A and a carboxylic acid ester solvent having a total carbon number of 4 to 8 to perform crystallization, and the crystals are precipitated at a temperature of the solution in the range of 10 to 45°C.
[0225] Specific examples of the carboxylic acid ester solvent having a total carbon number of 4 to 8 include ethyl acetate (total carbon number 4); ethyl propionate (total carbon number 5); butyl acetate (total carbon number 6); amyl acetate, isoamyl acetate, 2-methylbutyl acetate (total carbon number 7); n-hexyl acetate (total carbon number 8), etc. Among them, butyl acetate is particularly preferred.
[0226] The amount of the carboxylic acid ester solvent having 4 to 8 total carbon atoms used is in the range of 0.3 to 5 times by weight, more preferably 0.5 to 3 times by weight, and particularly preferably 0.5 to 2 times by weight, based on the compound A used.
[0227] As the chain aliphatic hydrocarbon solvent having 5 to 10 carbon atoms, specifically, for example, pentane, hexane, heptane, octane, and isooctane can be used, preferably a chain aliphatic hydrocarbon solvent having 6 to 8 carbon atoms, more preferably hexane, heptane, octane, or isooctane, further preferably hexane or isooctane, and particularly preferably isooctane.
[0228] The amount of the chain aliphatic hydrocarbon solvent having 5 to 10 carbon atoms used is in the range of 0.5 to 10 times by weight, more preferably 1 to 5 times by weight, further preferably 1.5 to 4 times by weight, particularly preferably 1.5 to 3 times by weight, relative to the amount of Compound A used.
[0229] When crystallization is precipitated, seed crystals may not be used, but it is preferred to use seed crystals. The crystal used as seed crystals is not limited, but crystal β is preferred, and crystals precipitated without seed crystals may be used as seed crystals.
[0230] As mentioned above, the crystal is precipitated when the temperature of the solution is in the range of 10 to 45° C., preferably in the range of 15 to 40° C., more preferably in the range of 20 to 40° C., and particularly preferably in the range of 20 to 35° C. After the crystal begins to precipitate, it is maintained at the same temperature to increase the amount of crystal precipitation. There is no particular limitation on the time of maintenance, but it is usually in the range of 1 to 120 hours.
[0231] After the amount of precipitated crystals is increased, the liquid containing the crystals may be cooled, and the final cooling temperature is preferably 10 to 30° C. The precipitated crystals may be isolated by filtering out the precipitated crystals.
[0232] The filtered crystals are preferably dried to remove the solvent used in the crystallization. The drying temperature is in the range of 25 to 140° C., more preferably in the range of 50 to 120° C. The drying may be carried out under normal pressure or under reduced pressure, but when it is industrially implemented, it is preferred to carry out under reduced pressure because the solvent can be removed more efficiently.
[0233] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0234] <Crystallization II> The crystal of the trisphenol compound represented by the chemical formula (A) of the present invention has an endothermic peak top temperature in the range of 103 to 116° C. obtained by differential scanning calorimetry. Hereinafter, the crystal may be referred to as “crystal II”. The peak top temperature is preferably in the range of 107 to 115° C., more preferably in the range of 110 to 115° C., and even more preferably in the range of 111 to 115° C.
[0235] <Crystal II-a> In Crystal II, there is a crystal having a peak at diffraction angles 2θ of 14.8°±0.2°, 15.2°±0.2°, 17.5°±0.2°, and 18.1°±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays. The crystal further preferably has peaks at diffraction angles 2θ of 12.5°±0.2°, 13.1°±0.2°, and 13.5°±0.2°, and further preferably has peaks at 16.4°±0.2°, 18.9°±0.2°, and 20.5°±0.2°. Hereinafter, the crystal is sometimes referred to as "Crystal II-a". In addition, based on the peak with the largest intensity, the relative intensity of these peaks is preferably greater than 10, and more preferably greater than 25. However, depending on the measuring device or conditions, and in the case of a mixture with other crystals, the relative intensity will change compared to a single substance. Therefore, the crystalline phase can be identified based on the analytical method of conventional powder X-ray diffraction analysis.
[0236] It is speculated that crystal II-a is a crystal that is solvated with toluene. In addition to being able to obtain compound A in a crystalline form, crystal II-a is very useful because it is excellent in handling and can improve operational efficiency in industrial production and application when compared with the properties of the conventionally known compound A.
[0237] In addition, by melting and distilling off toluene and then cooling, it can be used to produce Crystal I or Crystal α of Compound A having a low solvent content as described above.
[0238] <Method for producing crystal II-a> Crystal II-a of Compound A of the present invention can be produced by crystallizing a solution containing Compound A and toluene.
[0239] The amount of toluene used is in the range of 1 to 10 times by weight, more preferably 1.5 to 5 times by weight, further preferably 2 to 4 times by weight, and particularly preferably 2 to 3 times by weight, based on the amount of compound A used.
[0240] When crystallization is precipitated, seed crystals may not be used, but it is preferred to use seed crystals. The crystals used as seed crystals are not limited. The final cooling temperature is preferably 10 to 30° C. The precipitated crystals can be filtered out by filtering.
[0241] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0242] <Crystallization II-b> In Crystal II, there is a crystal having a form with peaks at diffraction angles 2θ of 11.4°±0.2°, 16.6°±0.2° and 17.8°±0.2° in the powder X-ray diffraction peak spectrum obtained by Cu-Kα rays. The crystal further preferably has a peak at a diffraction angle 2θ of 22.7°±0.2°. Hereinafter, the crystal is sometimes referred to as "Crystal II-b". In addition, based on the peak with the largest intensity, the relative intensity of these peaks is preferably 10 or more, more preferably 25 or more, but depending on the measuring device or conditions, in addition, in the case of a mixture with other crystals, the relative intensity will change compared to a single substance, so the crystalline phase can be identified based on the analytical method of the usual powder X-ray diffraction analysis.
[0243] It is speculated that crystal II-b is a crystal that is solvated with cyclohexane. In addition to being able to obtain compound A in a crystalline form, crystal II-b is very useful because it is excellent in handling and can improve operational efficiency in industrial production and application when compared with the properties of the previously known compound A.
[0244] Alternatively, by melting all or part of the solution to distill off cyclohexane and then cooling the solution, it is possible to produce Crystal I or Crystal α of Compound A having a low solvent content as described above.
[0245] The loose bulk density of the crystal II-b of compound A is preferably 0.3 to 0.6 g / cm 3 The loose bulk density is more preferably 0.3 to 0.5 g / cm 3 The range is more preferably 0.3 to 0.45 g / cm 3 The range is particularly preferably 0.3 to 0.4 g / cm 3 This form of crystal II-b has a high bulk density that is sufficiently advantageous in industrial production, and is therefore easy to handle, and contributes to efficient production of compound A, and is therefore preferred.
[0246] <Method for producing crystal II-b> Crystal II-b of Compound A of the present invention can be produced by crystallizing a solution containing Compound A and cyclohexane.
[0247] Since cyclohexane is a poor solvent having a low solubility for compound A, it is preferred to use a good solvent having a high solubility for compound A. Examples of such a good solvent include carboxylic acid ester solvents having a total carbon number of 4 to 8, and such solvents are preferred.
[0248] Specific examples of the carboxylic acid ester solvent having a total carbon number of 4 to 8 include: ethyl acetate (total carbon number 4); ethyl propionate (total carbon number 5); butyl acetate (total carbon number 6); amyl acetate, isoamyl acetate, 2-methylbutyl acetate (total carbon number 7); and n-hexyl acetate (total carbon number 8). Among them, butyl acetate is particularly preferred.
[0249] The amount of the good solvent (carboxylate solvent having 4 to 8 total carbon atoms) used is in the range of 0.3 to 5 times by weight, more preferably 0.5 to 3 times by weight, and particularly preferably 0.5 to 2 times by weight, based on the weight of the compound A used.
[0250] The amount of cyclohexane used is in the range of 1 to 10 times by weight, more preferably 1.5 to 5 times by weight, further preferably 1.5 to 4 times by weight, and particularly preferably 1.5 to 3 times by weight, relative to the amount of compound A used.
[0251] The total amount of the solvent used is 1.3 to 10 times by weight, more preferably 1.5 to 5 times by weight, further preferably 2 to 4 times by weight, and particularly preferably 2 to 3 times by weight, based on the amount of Compound A used.
[0252] When crystallization is precipitated, seed crystals may not be used, but it is preferred to use seed crystals. The crystals used as seed crystals are not limited. The final cooling temperature is preferably 10 to 30° C. The precipitated crystals can be filtered out by filtering.
[0253] In addition, since this series of operations may cause static electricity ignition due to oxidation or volatilization of the solvent, it is preferably performed in an inert gas environment with less oxygen, such as nitrogen or argon.
[0254] Example The present invention is further specifically described below by way of examples.
[0255] <Analysis method> 1. Differential Scanning Calorimetry (DSC) The obtained solid (crystal) was analyzed by differential scanning calorimetry (DSC) under the following conditions. The desolvation temperature or melting point was analyzed from the peak top temperature of the endothermic peak. In addition, the heat required to remove the solvating solvent per unit weight of the crystal was calculated from the area of the endothermic peak related to the desolvation of the crystal.
[0256] [Measurement conditions] Device: DSC7020 / manufactured by Hitachi High-Technologies Corporation Heating rate: 10℃ / min. Measuring temperature range: 30~200℃ Measurement environment: Nitrogen 50mL / min. Measured sample: 3mg 2. Thermogravimetric-differential thermal measurement The weight loss analysis of the obtained solid (crystal) was performed using a thermogravimetric-differential thermal analysis device (TG / DTA) under the following operating conditions. The weight loss observed before and after the endothermic peak was recorded.
[0257] [Measurement conditions] Device: STA-200 / manufactured by Hitachi High-Technologies Corporation Temperature: 30→250℃ (heating rate 10℃ / min.) Measurement environment: open, nitrogen 100mL / min. Test sample: 10 mg crystals 3. Analysis of the amount of solvent contained in the crystals The amount of solvent contained in the obtained solid (crystal) was analyzed under the following conditions.
[0258] <Analysis conditions 1 Headspace gas chromatography (HS-GC)> [Gas Chromatograph] Device: GC-2010 / Made by Shimadzu Corporation Detection type: FID Chromatographic column: GL Sciences, TC-160m, inner diameter 0.25mm, film thickness 0.25μm Carrier gas: Nitrogen Column temperature: 40°C (10 min.) → 20°C / min. to 300°C → 300°C (5 min.) Vaporization chamber temperature: 300℃ Control mode: Pressure Total flow rate: 8.5ml / min. Column flow rate: 0.92ml / min. Line speed: 19.9cm / sec. Purge flow rate: 3.0ml / min. Split ratio: 5.0 Detector temperature: 310°C Supplementary flow rate: 30.0ml / min. Hydrogen flow rate: 40.0ml / min. Air flow rate: 400.0ml / min. [HS Injector] Device: TurboMatrixHS40 / PerkinElmer Co., Ltd. Incubator temperature: 100°C Injection needle temperature: 105°C Transfer temperature: 105℃ Insulation time: 20min. Pressurization time: 3.0min. Extraction time: 0.5min. Injection time: 0.05min. GC cycle time: 44.0 min. HS carrier gas pressure: 154.0 kPa Headspace mode: Constant Vial venting: OFF <Measurement Condition 2 High Performance Liquid Chromatography (HPLC)> Apparatus: Shimadzu HPLC LC-20 series / manufactured by Shimadzu Corporation Pump: LC-20AT Column oven: CTO-20A Detector: SPD-20A Chromatographic column: Shim-Pack CLC-ODS, 6 mm × 15 cm / manufactured by Shimadzu GLC Corporation Incubator temperature: 50℃ Flow rate: 1.0mL / min. Mobile phase: (A) 0.2 vol% acetic acid aqueous solution, (B) methanol Gradient conditions: (A) Volume % (time elapsed from the start of analysis) 50% (0 min.) → 100% (30 min.) → 100% (45 min.) Sample injection volume: 20μL Detection wavelength: 280nm, 254nm 4. Analysis of the amount of solid adhering to the flask after filtration After the filtration operation is completed, the solvent used for the crystallization operation is added to the container to wash away the residual crystallization liquid. Methanol is added to the container and stirred at room temperature until the solid adhering to the container is completely dissolved. The obtained solution is analyzed by high performance liquid chromatography to quantify the concentration of compound A and calculate the amount of compound A adhering to the container.
[0259] 5. Powder X-ray Diffraction Analysis (PXRD) 0.1 g of the obtained solid (crystal) was filled in a sample filling portion of a glass test plate, and powder X-ray diffraction analysis was performed using the following apparatus and under the following conditions.
[0260] [Measurement conditions] Device: MiniFlex600-C / manufactured by Rigaku Co., Ltd. X-ray source: CuKα Scan axis: 2θ / θ Mode: Continuous Measuring range: 2θ=5°~90° Step size: 0.02° Speed measurement time: 10° / min. Entrance slit: 0.25° Receiving slit: 13.00mm Tube voltage: 40kV Tube current: 15mA 6. Determination of bulk density The value of the loose bulk density of the crystals obtained in the examples was calculated by dividing the weight of the crystals filled in the measuring cylinder by the volume value measured immediately after the crystals were filled in the measuring cylinder.
[0261] The tapped bulk density of the crystals obtained in the examples was calculated by dividing the weight of the crystals filled in the measuring cylinder by the volume of the crystals after the measuring cylinder was filled with the crystals and then manually shaken 300 times.
[0262] <Comparative Example 1> Crystallization experiment of compound A according to the conventionally known crystallization method (1) A crystallization experiment was conducted according to the description of Examples 3 and 4 of Patent Document 1 which describes a crystallization method using a mixed solvent of methyl isobutyl ketone and toluene.
[0263] As compound A, crystalline I・α (3.03 g) obtained in Example 1 described later was used, and it was added to a 100 mL test tube with o-cresol (4.23 g), methanol (0.30 g), methyl isobutyl ketone (0.82 g), toluene (2.44 g), and ultrapure water (0.29 g), and the mixture was heated to 60°C to dissolve. The amount of solvent used was 2.7 times the weight of compound A. After heating, the mixture was stirred at room temperature while cooling for one night to allow the prepared mixed solvent of methyl isobutyl ketone and toluene to recrystallize from the solution. However, no crystal precipitation was observed.
[0264] From the results of Comparative Example 1, it was confirmed that in the crystallization method (1) using a mixed solvent of toluene and methyl isobutyl ketone among the conventionally known crystallization methods, precipitation of crystals was not observed and crystals could not be obtained.
[0265] <Comparative Example 2> Crystallization experiment of compound A according to the conventionally known crystallization method (2) A crystallization experiment was performed according to the description of Examples in Patent Documents 2 to 5 which describe a crystallization method using decane as a solvent.
[0266] As compound A, crystal II (7.3 g: solid content 6.6 g) obtained in Example 1 described later was used, and it was added with decane in a 300 mL four-necked flask to prepare a suspension of crystals. After replacing the flask with nitrogen, it was heated until the liquid temperature reached 173°C, and decane was added until all the crystals were dissolved. The amount of decane used was 160.8 g, and the amount of solvent required was 24.4 times the weight of compound A.
[0267] Then, cooling was started to 98°C at a rate of 10°C / hour to recrystallize compound A from the prepared decane solution. Thus, immediately after cooling was started, the solvent and the oily target compound were separated to form an oily precipitation state. Then, the oily target compound adhered to the inner wall of the flask and solidified in the adhered state.
[0268] After turning off the power of the heater and cooling to 25°C, try to separate the solids attached and solidified on the inner wall of the flask using a Kiriyama funnel. First, filter the suspension containing the floating solids using a Kiriyama funnel (first filtration operation). Wash the filtered solids with decane (51.7 g), and air-dry the obtained solids on the Kiriyama funnel. However, the amount of the obtained solids was 0.3 g, and most of the residue was still attached to the inside of the flask.
[0269] Therefore, the attached solid was scraped off with a spatula, and the solid was filtered out with a Kiriyama funnel while using decane (75.5 g) to obtain a solid (5.0 g) (second filtration operation). Then, the filtered solid was transferred to a 50 mL eggplant flask, and the pressure was reduced to 1.0 kPa while heating at 60° C., and dried for 2 hours. 5.0 g of a dried solid was obtained.
[0270] On the other hand, after scraping off the attached solid with a scraper, the amount of the solid compound A adhering to the flask was quantified by the above method. As a result, 1.4 g of solid components remained on the flask. From the above results, it can be seen that at the time point after the first filtration operation, 6.4 g of solid components adhered to the flask, and the ratio was 98% by weight.
[0271] The results of Comparative Example 2 clearly show that among the conventionally known crystallization methods for compound A, the crystallization method (2) using decane requires a very large amount of solvent even when heated to a high temperature of 173° C., and the energy and time required for heating are also large, and the volumetric efficiency when producing compound A is very poor.
[0272] It was further clarified that a large amount of solids of Compound A adhered to the manufacturing equipment and were almost not available for filtering. When adhesion to the manufacturing equipment occurs, the solids cannot be discharged from the equipment, which not only leads to a significant decrease in yield, but also leads to the inability to continue production. The cleaning operation to remove the adhered solids may take time, or may require operators to enter the manufacturing equipment and perform the cleaning operation by hand, which is a highly dangerous operation.
[0273] As can be seen from the above, the solid of the conventionally known compound A has this property, and the conventionally known crystallization method (2) has problems due to this phenomenon, so it is not suitable for industrial production or its efficiency is very low.
[0274] <Example 1: Production of Crystal II and Crystal II-a> o-Cresol (975 g), methanol (132 g), and n-dodecyl mercaptan (50 g) were placed in a 5L four-necked flask, and hydrogen chloride gas was blown in until saturation while stirring at 25°C. Using a dropping funnel, a mixed solution of p-isopropenylacetophenone (322 g) and o-cresol (327 g) was added dropwise to the flask at a temperature of 26-30°C over 3.5 hours, and then stirred for 22.7 hours while maintaining the temperature.
[0275] Then, the reaction liquid was neutralized at a temperature of 25-37°C using 16% sodium hydroxide aqueous solution (865g), 75% phosphoric acid aqueous solution (4g), 35% hydrochloric acid (8g), and ultrapure water (22g) to neutralize the reaction liquid. The neutralized reaction liquid was heated to 113°C and the excess methanol was distilled off. The total weight of the distillate at this time was 952g.
[0276] Toluene (1296 g) and ultrapure water (503 g) were mixed with the residual liquid after distillation, and the mixture was dissolved in the oil layer by heating to 90°C, and the water layer was separated. New ultrapure water (403 g) was added to wash the oil layer at 80°C, and the water layer was separated to obtain the oil layer.
[0277] The internal liquid was heated to 165°C and the reduced pressure was 1.8 kPa to distill off toluene and excess o-cresol. The total weight of the distillate at this time was 1878 g.
[0278] Toluene (2087 g) was added to the residual liquid after distillation to lower the temperature of the liquid to 72° C., then the solution was cooled to 40° C. at a rate of 10° C. / hour and then allowed to cool to 25° C. to precipitate a solid.
[0279] The precipitated solid was filtered out using a centrifugal filter, and the flask after filtration and the filtered solid were washed with toluene (414 g). In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 8.5 g (0.9 wt %) of the solid component adhered to the flask relative to the theoretical yield of 938 g (based on p-isopropenylacetophenone).
[0280] The obtained solid (871 g) was placed in a 5 L eggplant-shaped flask, and the pressure was reduced to 0.4 kPa while heating at 65° C., and the mixture was dried for 4 hours.
[0281] The above operation yielded a solid (816 g) of the target compound Compound A. The yield was 78% based on the used p-isopropenylacetophenone. In addition, the obtained solid contained 9.6% toluene.
[0282] The obtained solid has a melting point as shown by the results of differential scanning calorimetry analysis, which indicates that it is a crystal. The melting point and desolvation temperature are 112°C. The differential scanning calorimetry (DSC) data are shown in Figure 1 From this analysis result, it was clear that the obtained crystal was Crystal II.
[0283] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 1. The PXRD measurement chart is shown in Figure 2 From the analysis results, it was clear that the obtained crystal was Crystal II-a.
[0284] From these analysis results, it was clear that the obtained crystals were Crystal II (Crystal II-a) of Compound A solvated with toluene.
[0285] [Table 1]
[0286] <Example 2: Production of Crystal I and Crystal α> Crystal II (Crystal II-a) (33.2 g: solid content 30.0 g) obtained in Example 1 was used as Compound A, and it was added to a 300 mL four-necked flask with ethylbenzene (75.1 g) to prepare a suspension of crystals. After replacing the flask with nitrogen, the liquid temperature was heated to 95°C to completely dissolve the crystals. The amount of ethylbenzene used was 2.5 times the weight of the solvent relative to Compound A.
[0287] Then, the solution was cooled to 37°C at a rate of 10°C / hour to recrystallize compound A from the prepared ethylbenzene solution. Solids began to precipitate at 75°C, and the amount of solids precipitated increased at 62°C. Then, the power of the heater was turned off and the solution was cooled to 25°C.
[0288] After cooling to 25°C, the precipitated solid was filtered out with a centrifugal filter, and the flask and the filtered solid were washed with ethylbenzene (15.6 g). In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 2.0 g (6.5% by weight) of the solid content adhered to the flask relative to 30.0 g of the solid content charged.
[0289] The filtered solid containing the solvent (45.8 g) was placed in an eggplant-shaped flask, and the pressure was reduced to 0.6 kPa while heating at 60° C., and the mixture was dried for 5 hours.
[0290] The above operation yielded a solid compound A (26.9 g) as the target compound. The yield was 89% based on the solid content charged. In addition, the obtained solid contained 1.4% by weight of ethylbenzene.
[0291] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point of 175°C. The differential scanning calorimetry (DSC) data are shown in Figure 3 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0292] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 2. The PXRD measurement chart is shown in Figure 4 From this analysis result, it was clear that the obtained crystal was crystal α.
[0293] From these analysis results, it was clear that the obtained crystal was Crystal I (Crystal α) of Compound A.
[0294] [Table 2]
[0295] <Example 3: Production of Crystal I and Crystal α> Crystal II (Crystal II-a) (33.1 g: solid content 29.9 g) obtained in Example 1 was used as Compound A, and it was added to a 300 mL four-necked flask with ethylbenzene (75.1 g) to prepare a suspension of crystals. After replacing the flask with nitrogen, the liquid temperature was heated to 135°C to completely dissolve the crystals. The amount of ethylbenzene used was 2.5 times the weight of the solvent relative to Compound A.
[0296] Then, the solution was cooled to 42°C at a rate of 10°C / hour to recrystallize compound A from the prepared ethylbenzene solution. Solids began to precipitate at 70°C, and the amount of solids precipitated increased at 64°C. Then, the power of the heater was turned off, and the solution was allowed to cool to 25°C.
[0297] After cooling to 25°C, the precipitated solid was filtered out with a centrifugal filter, and the flask and the filtered solid were washed with ethylbenzene (15.8 g). In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 1.3 g (4.3% by weight) of solid content adhered to the flask relative to 29.9 g of the solid content charged.
[0298] The filtered solid containing the solvent (50.0 g) was placed in an eggplant-shaped flask, and the pressure was reduced to 0.5 kPa while heating at 60° C., and the mixture was dried for 6.3 hours.
[0299] The above operation yielded a solid compound A (27.5 g) as the target compound. The yield was 90% based on the solid content charged. In addition, the obtained solid contained 1.8% by weight of ethylbenzene.
[0300] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point of 175°C. The differential scanning calorimetry (DSC) data are shown in Figure 5 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0301] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 3. The PXRD measurement chart is shown in Figure 6 From this analysis result, it was clear that the obtained crystal was crystal α.
[0302] From these analysis results, it was clear that the obtained crystal was Crystal I (Crystal α) of Compound A.
[0303] [Table 3]
[0304] <Example 4: Production of Crystal I and Crystal β> Crystal II (Crystal II-a) obtained in Example 1 (75.1 g: solid content 67.8 g) was used as Compound A, and it was placed in an eggplant-shaped flask, the pressure was reduced to 0.6 kPa, and the mixture was heated to 135° C. for 4.75 hours. The crystals solvated with toluene melted once at 110° C. and solidified during the heating operation at 135° C.
[0305] Then, ethylbenzene (174.4 g) was added to the eggplant-shaped flask containing the solidified compound A, and the solid was completely dissolved by heating at 150° C. The amount of ethylbenzene used was 2.6 times the weight of the solvent relative to the compound A.
[0306] Then, 125.1 g (34.9 g of solid content of compound A) of the prepared ethylbenzene solution was transferred to a 300 mL four-necked flask. After the four-necked flask was replaced with nitrogen, it was heated to a liquid temperature of 136°C, and after the crystals were completely dissolved, the solution was cooled to 38°C at a rate of 30°C / hour to recrystallize compound A from the prepared ethylbenzene solution. Then, the power of the heater was turned off and cooled to 25°C. After cooling to 25°C between the start of cooling and 64 hours, crystals precipitated and the amount of precipitation increased. The precipitated solid was filtered out with a centrifugal filter, and the filtered flask and the filtered solid were washed with ethylbenzene (17.7 g). In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 1.6 g (4.6 wt%) of solid content was adhered to the flask relative to the 34.9 g of solid content loaded.
[0307] The filtered solid containing the solvent (34.5 g) was placed in an eggplant-shaped flask, and the pressure was reduced to 0.5 kPa while heating at 60° C., and the mixture was dried for 3.75 hours.
[0308] The above operation yielded a solid (32.3 g) of compound A, which was the target compound. The yield was 91% based on the solid content charged. In addition, the obtained solid contained 1.4% by weight of ethylbenzene.
[0309] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point of 177°C. The differential scanning calorimetry (DSC) data are shown in Figure 7 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0310] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 4. The PXRD measurement chart is shown in Figure 8 From this analysis result, it was clear that the obtained crystal was crystal β.
[0311] From these analysis results, it was clear that the obtained crystal was Crystal I (Crystal β) of Compound A.
[0312] [Table 4]
[0313] <Example 5: Production of Crystal I and Crystal β> o-Cresol (199.9 g), methanol (26.5 g), and n-dodecyl mercaptan (5.0 g) were added to a 1L four-necked flask, and hydrogen chloride gas was blown in until saturation while stirring at 32°C. Using a dropping funnel, a mixed solution of p-isopropenylacetophenone (65.5 g) and o-cresol (67.8 g) was added dropwise to the flask at a temperature of 27-32°C over 3 hours and 10 minutes, and then stirred for 18 hours and 35 minutes while maintaining the temperature.
[0314] Then, the reaction solution was neutralized at a temperature of 25 to 45° C. using a 16% sodium hydroxide aqueous solution (179.7 g), a 75% phosphoric acid aqueous solution (0.5 g), and ultrapure water (10.0 g) to neutralize the solution.
[0315] Butyl acetate (137.7 g) was added, and the mixture was heated to 60°C to separate the water layer. New butyl acetate (58.1 g), isooctane (66.9 g), and ultrapure water (80.1 g) were added, and the oil layer was washed with water at 80°C, and the water layer was separated. Then, ultrapure water (81.2 g) was added again to wash the oil layer with water, and the water layer was separated.
[0316] The internal liquid was heated to 140°C and the reduced pressure was 6.4 kPa to distill off butyl acetate, isooctane and excess o-cresol. The total weight of the distillate at this time was 415.3 g.
[0317] To the residual liquid after distillation, butyl acetate (73.9 g) was added to prepare a butyl acetate solution. The obtained butyl acetate solution (55.2 g) was transferred to a 300 mL eggplant flask, heated at 100°C, and reduced to 1.0 kPa to recover excess butyl acetate. The weight of the recovered internal liquid was 43.6 g.
[0318] The inner solution was transferred to a 300 mL four-necked flask and ethylbenzene (82.3 g) was added. Crystalline I·β of compound A (0.04 g) was added at 99°C and the solution was cooled to 26°C at a rate of 10°C / hour. Then, the heater was turned off and the solution was allowed to cool to 25°C.
[0319] The precipitated solid was filtered out using a centrifugal filter, and the flask after filtration and the filtered solid were washed with ethylbenzene (20.2 g). In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 1.1 g (2.8% by weight) of the solid component adhered to the flask relative to the theoretical yield of 39.1 g (based on p-isopropenylacetophenone).
[0320] The obtained solid (42.2 g) was placed in a 300 mL eggplant-shaped flask, and the pressure was reduced to 0.6 kPa while heating at 60° C., and the mixture was dried for 3 hours and 15 minutes.
[0321] The above operation yielded a solid compound A (27.7 g) as the target compound. The yield was 69% based on the used p-isopropenylacetophenone. In addition, the obtained solid contained 0.2% by weight of butyl acetate, 1.5% by weight of ethylbenzene, and 0.5% by weight of o-cresol.
[0322] The obtained solid has a melting point as shown by the results of differential scanning calorimetry analysis, which indicates that it is a crystal. The melting point is 172°C. The differential scanning calorimetry (DSC) data are shown in Fig. 9 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0323] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 5. The PXRD measurement chart is shown in Fig.10 From this analysis result, it was clear that the obtained crystal was crystal β.
[0324] From these analysis results, it was clear that the obtained crystal was Crystal I (Crystal β) of Compound A.
[0325] [Table 5]
[0326] <Example 6: Production of a mixture of Crystal I and Crystal β and Crystal II and Crystal II-a> Crystal II (Crystal II-a) (33.1 g: solid content 29.9 g) obtained in Example 1 was used as Compound A, and it was added to a 300 mL four-necked flask with ethylbenzene (76.1 g) to prepare a suspension of crystals. After replacing the flask with nitrogen, the liquid temperature was heated to 135°C to completely dissolve the crystals. The amount of ethylbenzene used was 2.5 times the weight of the solvent relative to Compound A.
[0327] Then, the solution was cooled to 25°C at a rate of 30°C / hour to recrystallize compound A from the prepared ethylbenzene solution. After cooling to 25°C between the start of cooling and 98 hours, crystals precipitated and the amount of precipitation increased. The precipitated solid was filtered out with a centrifugal filter, and the filtered flask and the filtered solid were washed with ethylbenzene (16.1 g). In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 1.6 g (5.5% by weight) of solid content was adhered to the flask relative to the 29.9 g of solid content loaded.
[0328] The filtered solid containing the solvent (41.9 g) was placed in an eggplant-shaped flask, and the pressure was reduced to 0.5 kPa while heating at 60° C., and the mixture was dried for 3.5 hours.
[0329] Through the above operation, a solid (25.8 g) of compound A, which is the target compound, was obtained. The yield was 82% based on the solid content charged. In addition, the obtained solid contained 3.1% by weight of ethylbenzene and 2.2% by weight of toluene.
[0330] The results of differential scanning calorimetry analysis show that the obtained solid is a crystal having endothermic peaks at 103°C and 178°C. The differential scanning calorimetry (DSC) data are shown in Fig.11 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0331] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 6. The PXRD measurement chart is shown in Fig.12 From the analysis results, it was clear that the obtained crystals were a mixture of Crystal β and Crystal II-a.
[0332] From these analysis results, it is clear that the obtained crystals are a mixture of Crystal I (Crystal β) and Crystal II (Crystal II-a) of Compound A. From the above, it is known that the endothermic peak top temperature of 103°C is the melting point of Crystal II, and the endothermic peak top temperature of 178°C is the melting point of Crystal β.
[0333] [Table 6]
[0334] <Example 7: Production of a mixture of Crystal I, Crystal α, and Crystal β> Crystal II (Crystal II-a) (33.2 g: solid content 30.0 g) obtained in Example 1 was used as Compound A, and mixed xylene (75.6 g) was added to a 300 mL four-necked flask to prepare a suspension of crystals. After replacing the flask with nitrogen, the liquid temperature was heated to 94°C to completely dissolve the crystals. The amount of mixed xylene used was 2.5 times the weight of the solvent relative to Compound A.
[0335] Then, the solution was cooled to 35°C at a rate of 10°C / hour to recrystallize compound A from the prepared mixed xylene solution. Solids began to precipitate at 74°C, and the amount of precipitated solids increased at 65°C. Then, the power of the heater was turned off and the mixture was left to cool to 25°C.
[0336] After cooling to 25°C, the precipitated solid was filtered out with a centrifugal filter, and the flask after filtration and the filtered solid were washed by mixing xylene (16.2 g). In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 1.8 g (6.2% by weight) of solid content adhered to the flask relative to 30.0 g of the solid content charged.
[0337] The filtered solid containing the solvent (34.2 g) was placed in an eggplant-shaped flask, and the pressure was reduced to 1.1 kPa while heating at 60° C., and the mixture was dried for 4 hours.
[0338] Through the above operation, a solid (27.2 g) of compound A, which is the target compound, was obtained. The yield was 89% based on the solid content charged. In addition, the obtained solid contained 2.1% by weight of xylene.
[0339] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point of 177°C. Fig.13 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0340] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 7. The PXRD measurement chart is shown in Fig.14 From this analysis result, it is clear that the obtained crystal is a mixture of Crystal α and Crystal β.
[0341] [Table 7]
[0342] <Example 8: Production of Crystal I and Crystal α by Melting Operation> Crystal II (crystal II-a) (199 g) obtained in Example 1 as compound A was placed in a 1 L eggplant flask, heated at 135° C. while reducing the pressure to 1.5 kPa, and dried for 5 hours. During this period, the crystal melted and became oily, and then cooled to obtain a solid (181 g). The obtained solid contained 0.1% by weight of toluene.
[0343] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point of 173°C. Fig.15 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0344] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 8. The PXRD measurement chart is shown in Fig.16 From this analysis result, it was clear that the obtained crystal was crystal α.
[0345] From these analysis results, it was clear that the obtained crystal was Crystal I (Crystal α) of Compound A.
[0346] [Table 8]
[0347] <Example 9: Production of Crystal I (Crystal Ia) and Crystal α'> Crystal α (Crystal I) (13.7 g) obtained in Example 8 as Compound A and methanol (11.0 g) were added to a 200 mL eggplant flask and heated to 60° C. to dissolve. Ultrapure water (18.8 g) was added and stirred overnight while cooling to 25° C. The amount of solvent used was 2.2 times by weight relative to Compound A.
[0348] Since solid precipitation was observed in the internal solution, the inner wall was rubbed with a spatula to promote solid precipitation. After this operation, the mixture was further stirred overnight.
[0349] The precipitated solid was separated and taken out using a Kiriyama funnel, and the solid was washed with ultrapure water (20.1 g). In addition, after the crystallization liquid was transferred to the Kiriyama funnel, there was almost no residual solid in the flask, and almost no solid adhered to the inner wall of the flask. The obtained solid (18.9 g) was added to a 200 mL eggplant flask, heated at 60°C while reducing the pressure to 0.6 kPa, and dried for 3.5 hours to obtain a solid (13.9 g).
[0350] The obtained solid contained 2.0% by weight of water and 5.2% by weight of methanol.
[0351] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a desolvation temperature of 84°C and a melting point of 172°C. Fig.17 From this analysis result, it was clear that the obtained crystal was Crystal Ia.
[0352] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 10 or more based on the peak with the highest intensity are shown in Table 9. The PXRD measurement chart is shown in Fig.18 From this analysis result, it was clear that the obtained crystal was crystal α'.
[0353] From these analysis results, it was clear that the obtained crystal was Crystal Ia (Crystal α′) of Compound A.
[0354] [Table 9]
[0355] <Example 10: Production of Crystal I and Crystal α> Crystals α' (crystals Ia) (5.0 g) of compound A obtained in Example 9 were placed in a 50 mL eggplant flask, heated at 85° C., reduced pressure to 1.6 kPa, and dried for 3.25 hours. During this period, melting of the crystals was not observed and the crystals remained in a powdery state.
[0356] Through the above operation, crystals (4.8 g) containing 0.7 wt % of water were obtained.
[0357] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point of 171°C. Fig.19 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0358] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 10 or more based on the peak with the highest intensity are shown in Table 10. The PXRD measurement chart is shown in Fig. 20 From the analysis results, it is clear that the peaks appearing in the crystal α' obtained in Example 9 do not exist at the diffraction angles 2θ of 14.9°±0.2° and 22.5°±0.2°, and these peaks are considered to be the elements that distinguish "crystal α" from "crystal α'". It is also clear that the obtained crystal is crystal α.
[0359] From these analysis results, it was clear that the obtained crystal was Crystal I (Crystal α) of Compound A.
[0360] [Table 10]
[0361] <Example 11: Production of Crystal I (Crystal Ia) and Crystal α'> Crystal II (Crystal II-a) (33.4 g: solid content 30.3 g) obtained in Example 1 was used as Compound A, which was placed in an eggplant-shaped flask, reduced in pressure to 0.6 kPa, and heated to 135° C. for 2 hours.
[0362] Then, methanol (31.5 g) was added to the eggplant-shaped flask containing the solidified compound A, and the mixture was heated at 45° C. to completely dissolve the solid. The amount of methanol used was 1.0 times the weight of the compound A as a solvent.
[0363] Then, 61.4 g (30.1 g solid content) of the prepared methanol solution was transferred to a 300 mL four-necked flask. After the four-necked flask was replaced with nitrogen, the temperature was raised to 57°C, and ultrapure water (46.7 g) was added over 1 hour and 30 minutes while stirring the liquid in the range of 57 to 59°C. The amount of solvent used in the crystallization operation was 2.6 times the weight of compound A.
[0364] Then, the mixture was cooled at a rate of 9° C. / hour to 26° C. Then, the heater was turned off and the mixture was left to cool to 25° C. After cooling, stirring was continued for 39 hours, at which point solids were confirmed to be precipitated in the liquid in a dispersed state.
[0365] The slurry containing the precipitated solid was injected into a centrifugal filter, and the solid in the flask was injected into the centrifugal filter while using ultrapure water (75.1 g) to filter out the solid. In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 1.2 g (3.9 wt %) of the solid content adhered to the flask relative to 30.1 g of the solid content charged.
[0366] The results of differential scanning calorimetry analysis showed that the endothermic peak temperature of the obtained solid accompanying the evaporation of the attached solvent and desolvation was 104°C, and the melting point was 172°C. The differential scanning calorimetry (DSC) data are shown in Fig.21 From this analysis result, it is clear that the obtained crystal is Crystal I, and it is also suggested that it is Crystal Ia.
[0367] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 10 or more based on the peak with the highest intensity are shown in Table 11. The PXRD measurement chart is shown in Fig. 22 From this analysis result, it was clear that the obtained crystal was crystal α'.
[0368] From these analysis results, it was clear that the obtained crystal was Crystal I (Ia) of Compound A (Crystal α′).
[0369] [Table 11]
[0370] <Example 12: Production of Crystal I (Crystal Ia) and Crystal α> The crystals α' (crystals Ia) (63.9 g) of compound A obtained in Example 11 were placed in a 300 mL eggplant flask, decompressed to 0.7 kPa, dried at 30°C for 0.5 hours, 40°C for 1 hour, 40-60°C for 0.5 hours, and then dried at 60°C for 4.5 hours, with partial sampling during the drying process, for a total of 6.5 hours. During this period, no melting of the crystals was observed, and the crystals remained in a powdery state.
[0371] In addition, the crystals sampled during the drying operation are shown below.
[0372] [Crystallization 12-1] Drying temperature 40°C, drying time 1 hour and 30 minutes [Crystallization 12-2] Drying temperature 45°C, drying time 1 hour and 40 minutes [Crystallization 12-3] Drying temperature 60°C, 3 hours after drying [Crystallization 12-4] Time point when drying is completed Through the above operation, crystals [Crystals 12-4] (26.3 g) containing 0.5 wt % of methanol and 0.2 wt % of water were obtained.
[0373] (Differential scanning calorimetry analysis results) The differential scanning calorimetry (DSC) data of the crystals [Crystal 12-1], [Crystal 12-3], and [Crystal 12-4] obtained in the above drying operation are shown in Fig.23 , 24 and 25. As the drying progressed, the attached solvent of the crystals of compound A obtained in Example 11 decreased. From the DSC data, it can be seen that the size of the endothermic peak accompanying the evaporation of the attached solvent and desolvation became smaller, and endothermic peaks considered to be desolvation were observed at 81-85°C. It was also confirmed that the area of the endothermic peak accompanying desolvation (the amount of endothermic heat per 1 mg of crystal) decreased from 11.6 mJ / mg of [Crystal 12-3] to 5.5 mJ / mg of [Crystal 12-4]. It can be considered that the content of the solvated solvent in compound A was reduced by the drying operation, and the solvated crystals of compound A were changed to unsolvated crystals.
[0374] It was also clarified that the crystal of compound A obtained in Example 11 was crystal Ia among crystals I.
[0375] (Powder X-ray diffraction measurement results) Regarding the crystals obtained in the above drying operation, the diffraction angles 2θ (°) of the diffraction peaks of [Crystal 12-2], [Crystal 12-3] and [Crystal 12-4] measured by powder X-ray diffraction (PXRD) and the peaks with a relative intensity of 10 or more based on the peak with the highest intensity are shown in Tables 12, 13 and 14, respectively. The PXRD measurement charts are shown in Fig.26 , 27 and 28.
[0376] It is found that the peaks at diffraction angles 2θ of 7.5°, 15.0° and 22.5° appearing in the crystal α' obtained in Example 11 decrease with the progress of drying. Therefore, it is considered that these peaks are the elements that distinguish "crystal α" from "crystal α'".
[0377] From the PXRD analysis results of the final crystal [Crystal 12-4], it can be seen that since a peak characteristic of the crystal α' of compound A appears at 15.0° on the PXRD chart, it can be inferred that there is a trace amount of residue, but the relative intensity has been reduced to less than 10, so it can be seen that crystal α has been produced.
[0378] The results of the differential scanning calorimetry and powder X-ray diffraction measurement shown above suggest that desolvation proceeded due to drying.
[0379] [Table 12]
[0380] [Table 13]
[0381] [Table 14]
[0382] <Example 13: Production of Crystal I and Crystal α> Crystal II (Crystal II-a) (33.0 g: solid content 29.8 g) obtained in Example 1 was used as Compound A, and it was added to a 300 mL four-necked flask with butyl acetate (15.3 g) to prepare a suspension of crystals. After replacing the inside of the flask with nitrogen, the liquid temperature was heated to 100° C. to completely dissolve the crystals. The amount of butyl acetate used was 0.5 times the weight of the solvent relative to Compound A.
[0383] Then, isooctane (60.2 g) was added over 2 hours and 30 minutes while stirring the liquid in the flask at a liquid temperature of 92 to 101°C, so that compound A was recrystallized from the prepared butyl acetate solution. During the addition of isooctane, after the oil was precipitated, a waxy mass was temporarily formed, but the mass became dispersed by continuing to stir. The amount of solvent used in the crystallization operation was 2.5 times the weight of compound A.
[0384] Then, cool to 74°C at a rate of 10°C / hour. Then, turn off the power of the heater and let it cool to 25°C. The cooled liquid is in a state where the solid is evenly dispersed. Filter out the precipitated solid with a centrifugal filter, and wash the filtered flask and the filtered solid with isooctane (15.5g). In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 0.6g (2.1% by weight) of solid content was adhered to the flask relative to 29.8g of solid content loaded.
[0385] The filtered solid containing the solvent (33.8 g) was placed in an eggplant-shaped flask, and the pressure was reduced to 0.6 kPa while heating at 60° C., and the mixture was dried for 2.25 hours.
[0386] Through the above operation, a solid (26.9 g) of compound A, which is the target compound, was obtained. The yield was 90% based on the solid content charged. In addition, the obtained solid contained 0.2% by weight of butyl acetate.
[0387] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point of 177°C. The differential scanning calorimetry (DSC) data are shown in Fig.29 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0388] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 15. The PXRD measurement chart is shown in Fig.30 From this analysis result, it was clear that the obtained crystal was crystal α.
[0389] From these analysis results, it was clear that the obtained crystal was Crystal I (Crystal α) of Compound A.
[0390] [Table 15]
[0391] <Example 14: Production of Crystal I and Crystal β> Crystal II (Crystal II-a) (33.4 g: solid content 30.1 g) obtained in Example 1 was used as Compound A, and it was added to a 300 mL four-necked flask with butyl acetate (16.1 g) to prepare a suspension of crystals. After replacing the inside of the flask with nitrogen, the liquid temperature was heated to 125°C to completely dissolve the crystals. The amount of butyl acetate used was 0.5 times the weight of the solvent relative to Compound A.
[0392] The liquid was cooled to 27°C for 30 minutes while stirring, so that compound A was recrystallized from the prepared butyl acetate solution. Then, isooctane (60.8 g) was added over 2 hours and 30 minutes. During the addition of isooctane, a waxy substance accumulated at the bottom of the flask. Then, after continuing to stir for 44 hours, solids precipitated from the liquid and dispersed. The amount of solvent used in the crystallization operation was 2.6 times by weight relative to compound A.
[0393] The precipitated solid was injected into a centrifugal filter, and the solid in the flask was injected into the centrifugal filter while using isooctane (61.3 g) to filter out. In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 0.9 g (2.5% by weight) of solid content adhered to the flask relative to 30.1 g of the solid content charged.
[0394] The filtered solid containing the solvent (51.9 g) was placed in an eggplant-shaped flask, and the mixture was dried for 3 hours under reduced pressure to 1.5 kPa while being heated at 60° C.
[0395] Through the above operation, a solid (28.5 g) of compound A, which is the target compound, was obtained. The yield was 93% based on the solid content charged. In addition, the obtained solid contained 1.1% by weight of butyl acetate and 0.1% by weight of isooctane.
[0396] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point of 178°C. The differential scanning calorimetry (DSC) data are shown in Fig.31 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0397] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 16. The PXRD measurement chart is shown in Fig.32 From this analysis result, it was clear that the obtained crystal was crystal β.
[0398] From these analysis results, it was clear that the obtained crystal was Crystal I (Crystal β) of Compound A.
[0399] [Table 16]
[0400] <Example 15: Production of Crystal I and Crystal β> Crystal α (Crystal I) (3.0 g) obtained in Example 7 and tetralin (7.8 g) were added to a 100 mL test tube and heated to 125° C. to dissolve. The amount of solvent used was 2.6 times by weight relative to Compound A. After heating, the mixture was cooled and stirred at room temperature overnight.
[0401] The precipitated solid was separated and taken out using a Kiriyama funnel, and the solid was washed with tetralin (3.1 g) and isooctane (9.2 g). In addition, after the crystallization liquid was transferred to the Kiriyama funnel, there was almost no residual solid in the test tube, and almost no solid adhered to the inner wall of the test tube.
[0402] The obtained solid (3.8 g) was placed in a 50 mL eggplant-shaped flask, heated at 60°C and reduced in pressure to 1.0 kPa, and dried for 1 hour. Then, the temperature was raised to 100°C and dried for 3 hours to obtain a solid (2.6 g). The obtained solid contained 2.5% tetralin.
[0403] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point of 173°C. Fig.33 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0404] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 17. The PXRD measurement chart is shown in Fig.34 From this analysis result, it was clear that the obtained crystal was crystal β.
[0405] From these analysis results, it was clear that the obtained crystal was Crystal I (Crystal β) of Compound A.
[0406] [Table 17]
[0407] <Example 16: Production of Crystal II and Crystal II-b> Crystal α (crystal I) (2.1 g) of compound A obtained in Example 7 and butyl acetate (2.1 g) were added to a spiral tube and dissolved at room temperature. The resulting solution (2.0 g) was taken out to another spiral tube, cyclohexane (5.1 g) was added and stored in a refrigerator (4° C.). The amount of solvent used was 6.3 times the weight of compound A.
[0408] The precipitated crystals were separated and taken out using a Kiriyama funnel. In addition, after the crystallization liquid was transferred to the Kiriyama funnel, there was almost no residual solid in the spiral tube, and almost no solid adhered to the inner wall of the spiral tube. Then, it was air-dried on the Kiriyama funnel to obtain crystals (0.8 g).
[0409] Then, the crystal α (crystal I) (30.0 g) of compound A obtained in Example 7 and butyl acetate (35.1 g) were added to a 500 mL four-necked flask and heated to 76° C. Cyclohexane (60.2 g) was added to lower the liquid temperature in the flask to 54° C., and then the above crystal (0.03 g) was added, the power of the heater was turned off, and the mixture was left to cool to 25° C. The amount of solvent used was 3.2 times by weight relative to compound A.
[0410] The precipitated solid was filtered out using a centrifugal filter. In addition, after the crystallized liquid was transferred to the centrifugal filter, there was almost no residual solid in the flask, and almost no solid adhered to the inner wall of the flask. The filtered solid (18.5 g) was added to a 300 mL eggplant flask, heated at 65°C while reducing the pressure to 1.5 kPa, and dried for 4.3 hours.
[0411] Through the above operation, a solid (17.2 g) of the target compound Compound A was obtained. The obtained solid contained 12.9 wt % of cyclohexane and 0.8 wt % of butyl acetate.
[0412] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point and a desolvation temperature of 114°C. The differential scanning calorimetry (DSC) data are shown in Fig.35 From this result, it was clear that the obtained crystal was Crystal II.
[0413] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 18. The PXRD measurement chart is shown in Fig.36 From the analysis results, it was clear that the obtained crystal was Crystal II-b.
[0414] From these analysis results, it was clear that the obtained crystal was Crystal II of Compound A (Crystal II-b).
[0415] [Table 18]
[0416] <Example 17: Production of Crystal I and Crystal α by Melting Operation> Crystal II (Crystal II-b) (5.1 g) obtained in Example 16 was placed in a 50 mL eggplant flask, heated at 108°C, reduced pressure to 1.6 kPa, and dried for 2.5 hours. During this period, a portion of the solid melted and turned into an oily state, and then cooled to obtain a solid (4.3 g). The obtained solid contained 1.3% by weight of cyclohexane and 0.1% by weight of butyl acetate.
[0417] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point of 173°C. Fig.37 From the analysis results, it was clear that the obtained crystal was Crystal I.
[0418] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 19. The PXRD measurement chart is shown in Fig.38 From this analysis result, it was clear that the obtained crystal was Crystal α (Crystal I).
[0419] From these analysis results, it was clear that the obtained crystal was Crystal I (Crystal α) of Compound A.
[0420] [Table 19]
[0421] <Example 18: Production of Crystal II and Crystal II-b> Crystal II (crystal II-a) (33.3 g: solid content 30.3 g) of compound A obtained in Example 1 and butyl acetate (15.5 g) were added to a 300 mL four-necked flask, and nitrogen was passed through the flask to replace the atmosphere with nitrogen to prepare a suspension of crystals. After replacing the atmosphere in the flask with nitrogen, the liquid temperature was heated to 100° C. to dissolve all the crystals. The amount of butyl acetate used was 0.5 times the weight of the solvent relative to compound A.
[0422] Then, the temperature of the prepared butyl acetate solution was lowered to about 80° C., and while the solution was stirred in the range of 76 to 78° C., cyclohexane (61.1 g) was added over 2 hours and 30 minutes to recrystallize compound A. The amount of solvent used in the crystallization operation was 2.5 times the weight of compound A.
[0423] Then, cool to 29°C at a rate of 9°C / hour. Then, turn off the power of the heater and let it cool to 25°C. In the cooled liquid, the solid is uniformly dispersed. Filter out the precipitated solid with a centrifugal filter, and wash the filtered flask and the filtered solid with cyclohexane (16.4g). In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 0.5g (1.6% by weight) of solid content was adhered to the flask relative to 30.3g of solid content loaded.
[0424] The filtered solid containing the solvent (29.5 g) was placed in an eggplant-shaped flask, and the pressure was reduced to 0.6 kPa while heating at 60° C., and dried for 2.75 hours.
[0425] Through the above operation, a solid (29.1 g) of compound A, which is the target compound, was obtained. The yield was 82% based on the solid content charged. In addition, the obtained solid contained 13.8% by weight of cyclohexane and 0.7% by weight of butyl acetate.
[0426] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point of 113°C. The differential scanning calorimetry (DSC) data are shown in Fig.39 From this analysis result, it was clear that the obtained crystal was Crystal II.
[0427] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 20. The PXRD measurement chart is shown in Fig.40 From the analysis results, it was clear that the obtained crystal was Crystal II-b.
[0428] From these analysis results, it was clear that the obtained crystal was Crystal II of Compound A (Crystal II-b).
[0429] [Table 20]
[0430] <Reference Example 1> Crystal II (crystal II-a) (0.86 g) of compound A obtained in Example 1 and propylene glycol monomethyl ether (PGME) (0.64 g) were added to a spiral tube and dissolved at room temperature. The amount of solvent used was 0.8 times by weight relative to compound A. The resulting solution was left at room temperature for 21 days. No precipitated crystals were observed to adhere to the spiral tube, and the mixture was uniformly dispersed by stirring.
[0431] The precipitated solid was separated and taken out using a Kiriyama funnel, and washed with a 50% PGME aqueous solution (4.20 g). In addition, after the crystallization liquid was transferred to the Kiriyama funnel, there was almost no residual solid in the spiral tube, and almost no solid adhered to the inner wall of the spiral tube. The obtained solid was air-dried on the Kiriyama funnel. From the results of differential scanning calorimetry analysis, it was clear that the obtained solid (0.29 g) was a crystal with a melting point and desolvation temperature of 95°C.
[0432] Furthermore, the crystal α (crystal I) (5.01 g) of compound A obtained in Example 7 and PGME (5.04 g) were added to a 100 mL test tube and heated to 80°C to dissolve. The liquid temperature was lowered to 27°C, and ultrapure water (3.87 g) and the above crystals (31.3 mg) were added as seed crystals. The amount of solvent used was 1.8 times the weight of compound A. Then, the power of the heater was turned off and cooled to 25°C. No precipitated crystals were observed to adhere to the test tube, and they could be evenly dispersed by stirring.
[0433] The crystals were separated and taken out using a Kiriyama funnel, washed with a 50% PGME aqueous solution (21.76 g), and then air-dried. In addition, after the crystallization solution was transferred to the Kiriyama funnel, there was almost no residual solid in the test tube, and almost no solid adhered to the inner wall of the test tube. Thus, crystals (5.62 g) were obtained.
[0434] The obtained crystals (4.77 g) were placed in a 50 mL eggplant flask, heated at 60° C., reduced pressure to 1.5 kPa, and dried for 2 hours to obtain crystals (2.83 g). The crystals contained 15.8% PGME as a solvent component and 1.6% water.
[0435] <Reference Example 2> As compound A, crystal II (crystal II-a) (33.4 g: solid content 30.2 g) obtained in Example 1 was used, and propylene glycol monomethyl ether (PGME) (45.4 g) was added to a 300 mL four-necked flask to prepare a crystal suspension, and after replacing the flask with nitrogen, the liquid temperature was heated to 98° C. to completely dissolve the crystal. The amount of PGME used was 1.5 times the weight of the solvent relative to compound A.
[0436] Then, water (36.5 g) was added as a poor solvent for 70 minutes to recrystallize compound A from the prepared PGME solution. After addition, the temperature of the solution dropped to 89°C. Then, the solution was cooled to 35°C at a rate of 10°C / hour, and the power of the heater was turned off and cooled to 25°C. Stirring was continued for 46 hours from the time when cooling began, but no crystal precipitation was observed. Then, 0.1 g of the crystal obtained in Reference Example 1 was added as a seed crystal, and when the solution was left to stand at a temperature of 25°C, crystals precipitated, and the amount of crystals increased. The precipitated solid was filtered out with a centrifugal filter, and the filtered flask and the filtered solid were washed with water (16.1 g). In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 0.4 g (1.4 wt %) of solid components were adhered to the flask relative to the 30.1 g of solid components loaded.
[0437] The filtered solid containing the solvent (37.8 g) was placed in an eggplant-shaped flask, and the pressure was reduced to 1.1 kPa while heating at 60° C., and the mixture was dried for 3 hours.
[0438] The above operation yielded a solid (19.3 g) of the target compound Compound A. The yield was 53% based on the solid content charged. The crystals contained 16.3% PGME as a solvent component.
[0439] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal with a melting point and a desolvation temperature of 102°C. The differential scanning calorimetry (DSC) data are shown in Fig.41 .
[0440] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 21. The PXRD measurement chart is shown in Fig.42 .
[0441] [Table 21]
[0442] <Reference Example 3> Crystal α (Crystal I) (0.67 g) obtained in Example 7 and 1,4-dioxane (1.17 g) were added to a spiral tube and dissolved at 35°C. When isooctane (0.40 g) was added to the solution, separation into two layers was observed. The mixed solution (0.22 g) was added to isooctane (2.02 g) and allowed to stand at room temperature for 29 days. The precipitated solid was separated and taken out using a Kiriyama funnel, washed with isooctane (5.19 g), and air-dried on the Kiriyama funnel to obtain a solid (0.08 g).
[0443] Furthermore, the crystal α (crystal I) (5.11 g) and 1,4-dioxane (3.75 g) obtained in Example 7 were added to a 100 mL test tube, heated to 100 ° C to dissolve. The amount of 1,4-dioxane used was 0.7 times by weight relative to compound A, and the amount of solvent used was 2.7 times by weight relative to compound A. The internal temperature was lowered to 80 ° C, and isooctane (9.93 g) and the above solid (3.5 mg) were added as seed crystals. Then, the power of the heater was turned off and cooled to 25 ° C. The precipitated crystals were separated and taken out with a Kiriyama funnel, washed with isooctane (28.34 g) and air-dried to obtain a solid (5.79 g). The obtained solid (4.98 g) was added to a 50 mL eggplant flask, heated at 60 ° C while reducing the pressure to 1.5 kPa, and dried for 1 hour to obtain a solid (4.92 g) containing 17.5% of 1,4-dioxane as a solvent component.
[0444] <Reference Example 4> Crystal II (Crystal II-a) (32.9 g: solid content 29.7 g) obtained in Example 1 was used as Compound A, and it was added to a 300 mL four-necked flask with 1,4-dioxane (37.6 g) to prepare a suspension of crystals. After replacing the flask with nitrogen, the liquid temperature was heated to 99°C to completely dissolve the crystals. The amount of 1,4-dioxane used was 1.3 times the weight of the solvent relative to Compound A.
[0445] Then, isooctane (38.7 g) was added as a poor solvent over 70 minutes to recrystallize compound A from the prepared 1,4-dioxane solution. After the addition, the temperature of the solution dropped to 93°C. Then, the solution was cooled to 42°C at a rate of 10°C / hour, the power of the heater was turned off, and the solution was left to cool to 25°C. Stirring was continued for 24 hours from the start of cooling, but no precipitation of crystals was observed.
[0446] Therefore, 0.1 g of the crystals obtained in Reference Example 3 was added as seed crystals, and when stirring was continued at a solution temperature of 25°C, crystals precipitated and the amount of crystals increased. When the liquid was injected to filter out the solid with a centrifugal filter, the solid did not flow out of the flask. Therefore, isooctane (45.7 g) was added to the flask, and the solid was dispersed and flowed into the centrifugal filter. After filtering out the solid, the filtered flask and the filtered solid were washed with isooctane (73.6 g). In addition, the amount of solid compound A adhering to the flask after the filtration operation was quantified by the above method. As a result, 6.5 g (21.9 wt %) of solid components were adhered to the flask relative to the 29.7 g of solid components loaded.
[0447] The filtered solid containing the solvent (56.5 g) was placed in an eggplant-shaped flask, and the pressure was reduced to 1.1 kPa while heating at 60° C., and the mixture was dried for 3.3 hours.
[0448] The above operation yielded a solid (25.9 g) of the target compound Compound A. The yield was 74% based on the solid content charged. The crystals contained 15.5% of 1,4-dioxane as a solvent component.
[0449] The results of differential scanning calorimetry analysis showed that the obtained solid was a crystal having a melting point and a desolvation temperature of 120°C. The differential scanning calorimetry (DSC) data are shown in Fig.43 .
[0450] In addition, the diffraction angle 2θ (°) of the diffraction peaks appearing in the powder X-ray diffraction (PXRD) measurement of the obtained crystals and the peaks having a relative intensity of 25 or more based on the peak with the highest intensity are shown in Table 22. The PXRD measurement chart is shown in Fig.44 .
[0451] [Table 22]
[0452] <Measurement of bulk density of crystals> The loose bulk density and tapped bulk density of the crystals of Compound A obtained in Examples 2 to 4, 7, 13 and 18 were measured by the above-mentioned analytical method. The results are shown in Table 23.
[0453] In addition, the crystals obtained in Example 6, Reference Example 1 and Reference Example 2 become lumps during crystallization, filtration or drying, and need to be broken up with a spatula for handling. Therefore, they are not uniform powders, and the measured value of bulk density varies depending on the degree of breaking of the lumps, so it is impossible to measure the accurate bulk density.
[0454] [Table 23]
[0455] From the results of Examples 1, 16 and 18, it is clear that the crystals II (crystals II-a, crystals II-b) of compound A of the present invention do not become oily, and the crystals of compound A can be precipitated from a crystallization liquid containing a small amount of solvent, and the crystals hardly adhere to the inner wall of the flask, and can be evenly dispersed in the liquid by stirring, and can be easily filtered out. It can be seen that the problems of the solid obtained by the conventionally known crystallization method of compound A are solved, and it is easy to handle during industrial production, and compound A can be efficiently produced.
[0456] It is clear from the results of Examples 1, 16 and 18 that the method for obtaining Crystal II (Crystal II-a, Crystal II-b) of Compound A of the present invention can precipitate Compound A in the form of crystals using a small amount of solvent without becoming an oily precipitate, and the precipitated crystals hardly adhere to the inner wall of the flask, can be uniformly dispersed in the liquid by stirring, and can be easily filtered out, thereby solving the problems of the conventionally known crystallization method and enabling efficient industrial production of Compound A in the form of crystals.
[0457] Furthermore, the bulk density of the crystal II-b obtained in Example 18 was measured to be 0.30 g / cm 3 The above-described industrial production has a sufficiently high bulk density, is easy to handle, and contributes to efficient production of Compound A.
[0458] However, since the Crystal II (Crystal II-a, Crystal II-b) still contains a large amount of solvent even after being dried under heating and reduced pressure, and since the melting point and desolvation temperature are the same, it is clear that there is still another problem that the solvent in the crystal must be melted to be removed.
[0459] From the results of Example 8 and Example 17, it is clear that Crystal II (Crystal II-a, Crystal II-b) of Compound A of the present invention can be melted to remove the solvent and then cooled to produce Crystal I and Crystal α with a low solvent content. Since the thus obtained Crystal I and Crystal α have a low solvent content, the amount of solvent exposure can be reduced during the storage and transportation of Compound A and when the crystal is used to produce a resin or a derivative, thereby contributing to the health of handling workers and the protection of the environment.
[0460] From the results of Examples 9 to 12, it is clear that the crystal I (crystal α) of compound A of the present invention can precipitate compound A in the form of crystals by using a small amount of solvent, and the crystals hardly adhere to the inner wall of the flask, and can be evenly dispersed in the liquid by stirring, and can be easily filtered out. It can be seen that the problems of the solid obtained by the conventionally known crystallization method of compound A are solved, and it is easy to handle during industrial production, and compound A can be efficiently produced.
[0461] Furthermore, it was found that even if Crystal Ia (Crystal α') in Crystal I is a crystal solvated with methanol, the solvent can be removed without melting. It was also found that Crystal I (Crystal α) with a low solvent content and easy to handle in a powder form can be produced. That is, it was found that another problem identified in Crystal II (Crystal II-a, Crystal II-b) can also be solved.
[0462] It is known that the method for obtaining the crystal Ia (crystal α') of the compound A of the present invention can precipitate the compound A in the form of crystals using a small amount of solvent, and the precipitated crystals hardly adhere to the inner wall of the flask, can be uniformly dispersed in the liquid, and can be easily filtered out. Therefore, it can solve the problems of the conventionally known crystallization method, and can efficiently produce the compound A in the form of crystals industrially.
[0463] Furthermore, it is found that this method can produce crystal α', and even if the precipitated crystal is a crystal solvated with methanol, the solvated methanol can be removed without melting, thereby producing crystal α with a low solvent content and easy to handle in a powder form.
[0464] It is found that the crystal α produced by the production method of the present invention has a low solvent content and is easily handled in a powder form, and that the compound A can be produced industrially efficiently in the form of a crystal.
[0465] It is clear from the results of Examples 2 to 7 and Examples 13 to 15 that the crystals of compound A of the present invention can be precipitated from a crystallization liquid containing a small amount of solvent, and the crystals hardly adhere to the inner wall of the flask, and can be evenly dispersed in the liquid by stirring, and can be easily filtered out. It can be seen that the problems of the solid obtained by the conventionally known crystallization method of compound A are solved, and it is easy to handle during industrial production, and compound A can be efficiently produced.
[0466] It was also clarified that compound A can be produced in the form of crystals with a low solvent content by drying without solvating with the solvent in the crystallization liquid from the beginning of precipitation, and that the heat required for desolvation can be reduced, thereby efficiently producing compound A.
[0467] Furthermore, from the results of the bulk density measurements of the crystals obtained in Examples 2, 3, 4, 7 and 13, it can be seen that the bulk density of the crystals is 0.30 g / cm 3 The above-described industrial production has a sufficiently high bulk density, is easy to handle, and contributes to efficient production of Compound A.
[0468] From the results of Examples 2 to 7 and Examples 13 to 15, it can be seen that the method for producing the crystal I of compound A of the present invention can precipitate compound A in the form of crystals using a small amount of solvent, and the precipitated crystals hardly adhere to the inner wall of the flask, can be evenly dispersed in the liquid, and can be easily filtered out. Therefore, it can solve the problems of the conventionally known crystallization method and can efficiently produce compound A in the form of crystals industrially.
[0469] It is further understood that since it is possible to produce a powdery crystal I from which the solvent is removed by drying without undergoing solvation with the solvent in the crystallization liquid from the beginning of precipitation, without the need for melting and desolvation, it is possible to produce a crystal α having a low solvent content and being easy to handle in a powdery state.
[0470] In addition, in this production method, from the results of Examples 2 to 7 and 15, it is understood that by using ethylbenzene, mixed xylenes, or tetralin as the crystallization solvent, crystals of Compound A can be precipitated without becoming an oily precipitate.
[0471] Furthermore, from the results of measuring the bulk density of the crystals obtained in Examples 2, 3, 4, 7 and 13, it can be seen that the present production method can produce a crystal with a loose bulk density of 0.30 g / cm 3 In the above industrial production, crystals of Compound A having a sufficiently advantageous high bulk density can be produced, and can be easily handled, thereby contributing to efficient production of Compound A.
[0472] From the results of Examples 2, 3 and 13, and Examples 9 to 12, it is clear that the crystal α of compound A of the present invention can precipitate the crystal of compound A from the crystallization liquid with a small amount of solvent, and the crystal hardly adheres to the inner wall of the flask, can be evenly dispersed in the liquid by stirring, and can be easily filtered out. It can be seen that it solves the problems of the solid obtained by the conventionally known crystallization method of compound A, is easy to handle during industrial production, and can efficiently produce compound A.
[0473] Furthermore, it is clear from the results of Examples 2, 3 and 13 that no solvation occurs with the solvent in the crystallization liquid from the beginning of precipitation, and compound A can be produced in the form of crystals with a low solvent content after drying, and the heat required for desolvation can be reduced, thereby efficiently producing compound A.
[0474] Furthermore, from the measurement results of the bulk density of the crystal α obtained in Examples 2, 3 and 13, it can be seen that when the loose bulk density is 0.30 g / cm 3 The above-described high bulk density is sufficiently advantageous in industrial production, so that the compound can be easily handled and contributes to efficient production of the compound A.
[0475] From the results of Examples 2, 3 and 13, it can be seen that the method for producing crystalline α of compound A of the present invention can precipitate compound A in the form of crystals using a small amount of solvent, and the precipitated crystals will hardly adhere to the inner wall of the flask, can be evenly dispersed in the liquid, and can be easily filtered out. Therefore, it can solve the problems of the previously known crystallization methods and can efficiently produce compound A in the form of crystals industrially.
[0476] Furthermore, from the measurement results of the bulk density of the crystal α obtained in Examples 2, 3 and 13, it can be seen that when the loose bulk density is 0.30 g / cm 3 The above-described high bulk density is sufficiently advantageous in industrial production, so that the compound can be easily handled and contributes to efficient production of the compound A.
[0477] From the results of Examples 4, 5, 14 and 15, it is clear that the crystal β of compound A of the present invention can precipitate the crystal of compound A from the crystallization liquid with a small amount of solvent, and the crystal hardly adheres to the inner wall of the flask, and can be evenly dispersed in the liquid by stirring, and can be easily filtered out. It can be seen that the problems of the solid obtained by the conventionally known crystallization method of compound A are solved, and it is easy to handle during industrial production, and compound A can be efficiently produced.
[0478] It was also clarified that compound A can be produced in the form of crystals with a low solvent content by drying without solvating with the solvent in the crystallization liquid from the beginning of precipitation, and that the heat required for desolvation can be reduced, thereby efficiently producing compound A.
[0479] Furthermore, the bulk density of the crystal β obtained in Example 4 was measured to be 0.40 g / cm 3 In the above industrial production, the high bulk density is more advantageous, so that the compound can be easily handled and can be efficiently produced.
[0480] From the results of Examples 4, 5, 14 and 15, it can be seen that the method for producing crystalline β of compound A of the present invention can precipitate compound A in the form of crystals using a small amount of solvent, and the precipitated crystals hardly adhere to the inner wall of the flask, can be evenly dispersed in the liquid, and can be easily filtered out. Therefore, it can solve the problems of the previously known crystallization methods and can efficiently produce compound A in the form of crystals industrially.
[0481] It was further clarified that since it is possible to produce crystalline β in a powder form from which the solvent can be removed by drying without being solvated with the solvent in the crystallization liquid from the beginning of precipitation, without the need for melting and desolvation, it is a method for producing crystalline β with a low solvent content and easy to handle in a powder form.
[0482] Furthermore, from the measurement results of the bulk density of the crystal β obtained in Example 4, it can be seen that by this production method, a loose bulk density of 0.40 g / cm 3 In the above industrial production, crystals of Compound A having a sufficiently advantageous high bulk density can be produced, and can be easily handled, so that Compound A can be produced efficiently.
Claims
1. A crystal of a triphenol compound represented by chemical formula (A), characterized in that: The peak top temperature of the endothermic peak obtained by differential scanning calorimetry analysis is in the range of 168 to 180°C. [Chemistry 1] 。 2. The crystal according to claim 1, characterized in that Loose bulk density is 0.3~0.8g / cm 3 range.
3. The crystal according to claim 1, characterized in that The content ratio of the organic solvent in the crystal is 10% by weight or less.
4. The crystal according to claim 1, characterized in that The purity expressed by area % in liquid chromatography analysis was in the range of 90% to 100%.
5. A method for producing the crystal according to claim 1, characterized in that: The crystallization is carried out from a solution containing the triphenol compound represented by the chemical formula (A) and an alkylbenzene solvent having a total carbon number of 8 to 10.
6. A method for producing the crystal according to claim 1, characterized in that: Crystallization is performed by mixing a chain aliphatic hydrocarbon solvent having 5 to 10 carbon atoms into a solution containing the triphenol compound represented by the chemical formula (A) and a carboxylic acid ester solvent having 4 to 8 carbon atoms in total.
7. A method for producing the crystal according to claim 1, characterized in that: Crystallization is performed by mixing water into a solution containing the trisphenol compound represented by the chemical formula (A) and an alcohol solvent having 1 to 4 carbon atoms.
8. A method for producing the crystal according to claim 1, characterized in that: When crystals of the triphenol compound represented by the chemical formula (A) are heated to 30° C. to 170° C., the crystals have one endothermic peak top temperature in the range of 76° C. to 86° C. and one in the range of 168° C. to 180° C. as determined by differential scanning calorimetry.
9. A method for producing the crystal according to claim 1, characterized in that: Crystals of the triphenol compound represented by the chemical formula (A) are melted to distill off toluene, and then cooled, wherein the crystals have peaks at diffraction angles 2θ of 14.8°±0.2°, 15.2°±0.2°, 17.5°±0.2°, and 18.1°±0.2° in a powder X-ray diffraction peak pattern obtained by Cu-Kα radiation.
10. A method for producing the crystal according to claim 1, characterized in that: The crystals of the triphenol compound represented by the chemical formula (A) are melted to distill off cyclohexane and then cooled. The crystals have peaks at diffraction angles 2θ of 11.4°±0.2°, 16.6°±0.2° and 17.8°±0.2° in a powder X-ray diffraction peak pattern obtained by Cu-Kα radiation.
11. A crystal of a triphenol compound represented by chemical formula (A), characterized in that: In the powder X-ray diffraction peak spectrum obtained by Cu-Kα radiation, there are peaks at diffraction angles 2θ of 13.9°±0.2°, 15.8°±0.2°, and 17.0°±0.2°. [Chemistry 2] 。 12. The crystal according to claim 11, characterized in that Loose bulk density is 0.3~0.5g / cm 3 range.
13. The crystal according to claim 11, characterized in that The content ratio of the organic solvent in the crystal is 5% by weight or less.
14. The crystal according to claim 11, characterized in that The purity expressed by area % in liquid chromatography analysis was in the range of 90% to 100%.
15. A method for producing the crystal according to claim 11, characterized in that: The crystallization is carried out from a solution containing the triphenol compound represented by the chemical formula (A) and an alkylbenzene solvent having a total carbon number of 8 to 10, and the crystals are precipitated at a temperature of the solution in the range of 50 to 75°C.
16. A method for producing the crystal according to claim 11, characterized in that: The crystallization is carried out by mixing a linear aliphatic hydrocarbon solvent having 5 to 10 carbon atoms into a solution containing the triphenol compound represented by the chemical formula (A) and a carboxylic acid ester solvent having 4 to 8 total carbon atoms, and the crystals are precipitated at a temperature of 50 to 110° C. of the solution.
17. A method for producing the crystal according to claim 11, characterized in that: Crystals of the triphenol compound represented by the chemical formula (A) are heated to 30° C. to 170° C., wherein the crystals have peaks at diffraction angles 2θ of 13.9°±0.2°, 15.0°±0.2°, 15.8°±0.2°, and 17.0°±0.2° in a powder X-ray diffraction peak pattern obtained by Cu—Kα radiation.
18. A method for producing the crystal according to claim 11, characterized in that: Crystals of the triphenol compound represented by the chemical formula (A) are melted to distill off toluene, and then cooled, wherein the crystals have peaks at diffraction angles 2θ of 14.8°±0.2°, 15.2°±0.2°, 17.5°±0.2°, and 18.1°±0.2° in a powder X-ray diffraction peak pattern obtained by Cu-Kα radiation.
19. A method for producing the crystal according to claim 11, characterized in that: The crystals of the triphenol compound represented by the chemical formula (A) are melted to distill off cyclohexane and then cooled. The crystals have peaks at diffraction angles 2θ of 11.4°±0.2°, 16.6°±0.2° and 17.8°±0.2° in a powder X-ray diffraction peak pattern obtained by Cu-Kα radiation.
20. A crystal of a triphenol compound represented by chemical formula (A), characterized in that: In the powder X-ray diffraction peak spectrum obtained by Cu-Kα radiation, there are peaks at diffraction angles 2θ of 13.9°±0.2°, 15.0°±0.2°, 15.8°±0.2° and 17.0°±0.2°, [Chemistry 3] 。 21. A method for producing the crystal according to claim 20, characterized in that: Crystallization is performed by mixing water into a solution containing the triphenol compound represented by the chemical formula (A) and methanol.
22. A crystal of a triphenol compound represented by chemical formula (A), characterized in that: In the powder X-ray diffraction peak spectrum obtained by Cu-Kα radiation, there are peaks at diffraction angles 2θ of 11.4°±0.2°, 14.0°±0.2°, and 16.3°±0.2°. [Chemistry 4] 。 23. The crystal according to claim 22, characterized in that Loose bulk density is 0.4~0.8g / cm 3 range.
24. The crystal according to claim 22, characterized in that The content ratio of the organic solvent in the crystal is 5% by weight or less.
25. The crystal according to claim 22, characterized in that The purity expressed by area % in liquid chromatography analysis was in the range of 90% to 100%.
26. A method for producing the crystal according to claim 22, characterized in that: The crystallization is carried out from a solution containing the triphenol compound represented by the chemical formula (A) and an alkylbenzene solvent having a total carbon number of 8 to 10, and the crystals are precipitated at a temperature of the solution in the range of 10 to 45°C.
27. A method for producing the crystal according to claim 22, characterized in that: Crystallization is performed by mixing a linear aliphatic hydrocarbon solvent having 5 to 10 carbon atoms into a solution containing the triphenol compound represented by the chemical formula (A) and a carboxylic acid ester solvent having 4 to 8 total carbon atoms, and crystals are precipitated at a temperature of 10 to 45° C. on the solution.
28. A crystal of a triphenol compound represented by chemical formula (A), characterized in that: The peak temperature of the endothermic peak obtained by differential scanning calorimetry analysis is in the range of 103~116℃. [Chemistry 5] 。 29. The crystal according to claim 28, characterized in that In the powder X-ray diffraction peak pattern obtained by Cu—Kα rays, there are peaks at diffraction angles 2θ of 14.8°±0.2°, 15.2°±0.2°, 17.5°±0.2°, and 18.1°±0.2°.
30. A method for producing the crystal according to claim 28 or 29, characterized in that: Crystallization is performed from a solution containing the trisphenol compound represented by the chemical formula (A) and toluene.
31. The crystal according to claim 28, characterized in that In the powder X-ray diffraction peak spectrum obtained by Cu—Kα rays, there are peaks at diffraction angles 2θ of 11.4°±0.2°, 16.6°±0.2°, and 17.8°±0.2°.
32. The crystal according to claim 31, characterized in that Loose bulk density is 0.3~0.6g / cm 3 range.
33. A method for producing the crystal according to claim 28 or 31, characterized in that: Crystallization is performed from a solution containing the triphenol compound represented by the chemical formula (A) and cyclohexane.
Citation Information
Patent Citations
Triphenol compound
JP1987084035A
Ionizing radiation sensitive resin composition
JP1992251849A
Positive photoresist composition
JP1998097075A
Method of producing trisphenol derivatives
KR101786888B1
Method of producing trisphenol derivatives
KR1020170006311A